Aberrant splicing as potential modifier of the phenotype of junctional epidermolysis bullosa - Mittwollen, R.; Wohlfart, S.; Park, J.; Grosch, Ella; Has, C.; Hohenester, E.; Schneider, Holm; Hammersen, Johanna (Journal of the European Academy of Dermatology and Venereology, 2020)
Background: A lack or dysfunction of the anchoring protein laminin-332 in the basement membrane leads to the skin blistering disorder junctional epidermolysis bullosa (JEB). The mutation c.628G>A in the gene LAMB3 encoding the laminin β3-chain is associated with generalized intermediate JEB; it may introduce an amino acid substitution (p.Glu210Lys) or disrupt splicing. Objective: This retrospective study aimed at determining the effects of aberrant splicing on the JEB phenotype. Methods: LAMB3 transcription was analysed in two siblings compound heterozygous for the LAMB3 mutations p.Glu210Lys and p.Arg635* with a diverging JEB phenotype from late childhood on. Laminin-332 levels in skin sections and in cultured keratinocytes were investigated by immunofluorescence staining. Real-time PCR was used to quantify LAMB3 expression in keratinocytes. RNA splice variants were identified by subcloning of a LAMB3 cDNA fraction and subsequent DNA sequencing. Structural models of laminin-332 helped to assess the impact of certain mutations on laminin-332 folding. Results: Both siblings showed diminished LAMB3 expression. Laminin-332 was equally reduced in skin sections obtained during infancy but differed in keratinocytes isolated during adolescence. Although aberrant LAMB3 splicing with 26 variants was detected in both patients, splicing differed significantly: the full-length LAMB3 transcript harbouring the p.Glu210Lys mutation was found more often in the patient affected less severely (14/108 vs. 5/106 clones; P = 0.03). Structural modelling predicted that several deletions in LAMB3, but not the point mutation p.Glu210Lys, have an effect on laminin-332 folding and secretion. Conclusions: Differential LAMB3 mRNA splicing in the patients may explain the disparate JEB phenotype. By elucidating the regulation of laminin-332 gene expression, these findings may contribute to the development of therapeutic strategies for JEB and might help to understand phenotype modification by splice-site mutations in other hereditary diseases.
CRIS-Team Scopus Importer:2020-06-02

A Causal Treatment for X-Linked Hypohidrotic Ectodermal Dysplasia: Long-Term Results of Short-Term Perinatal Ectodysplasin A1 Replacement - Schneider, Holm; Schweikl, Christine; Faschingbauer, Florian; Hadj-Rabia, Smail; Schneider, Pascal (International Journal of Molecular Sciences, 2023)
X-linked hypohidrotic ectodermal dysplasia (XLHED), caused by a genetic deficiency of ectodysplasin A1 (EDA1), is a rare developmental disorder of ectodermal derivatives such as hair, sweat glands, and teeth. The absence of sweat glands and perspiration can evoke life-threatening hyperthermia. As molecular genetic findings are not always conclusive, the concentrations of circulating EDA1 may help to distinguish between total and partial EDA1 deficiencies. We previously treated nine male patients with obvious signs of XLHED with a recombinant EDA1 replacement protein, Fc-EDA, either shortly after birth (n = 3) or by prenatal administration in gestational week 26 and beyond (n = 6). Here, we present the long-term follow-up for up to six years. In patients who had received Fc-EDA after birth, neither sweat glands nor sweating ability were detected at the age of 12–60 months. In contrast, prenatal EDA1 replacement resulted in ample sweat gland development and pilocarpine-inducible sweating in all treated subjects, who also attained more permanent teeth than their untreated affected relatives. Normal perspiration has persisted for six years in the two oldest boys treated repeatedly with Fc-EDA in utero. When they had a sauna, adequate thermoregulation was evidenced. Lower sweat production after single prenatal dosing may indicate a dose–response relationship. The absence of circulating EDA1 in five prenatally treated subjects proved that these children would have been unable to perspire if they had been left untreated. The sixth infant was shown to produce an EDA1 molecule that, albeit interacting with its cognate receptor, cannot activate EDA1 signaling. In conclusion, a causal treatment of XLHED before birth is feasible.
CRIS-Team Scopus Importer:2023-05-12
Keywords: AlphaLisa; ectodermal dysplasia; ectodysplasin A; prenatal therapy; protein replacement; sweat glands; tooth development

Activation of canonical Wnt signalling is required for TGF-β-mediated fibrosis - Akhmetshina, Alfiya; Palumbo, Katrin; Dees, Clara; Bergmann, Christina; Venalis, Paulius; Zerr, Pawel; Horn, Angelika; Kireva, Trayana; Beyer, Christian; Zwerina, Jochen; Schneider, Holm; Sadowski, Anika; et al. (Nature Communications, 2012)
The transforming growth factor-β (TGF-β) signalling pathway is a key mediator of fibroblast activation that drives the aberrant synthesis of extracellular matrix in fibrotic diseases. Here we demonstrate a novel link between transforming growth factor-β and the canonical Wnt pathway. TGF-β stimulates canonical Wnt signalling in a p38-dependent manner by decreasing the expression of the Wnt antagonist Dickkopf-1. Tissue samples from human fibrotic diseases show enhanced expression of Wnt proteins and decreased expression of Dickkopf-1. Activation of the canonical Wnt pathway stimulates fibroblasts in vitro and induces fibrosis in vivo. Transgenic overexpression of Dickkopf-1 ameliorates skin fibrosis induced by constitutively active TGF-β receptor type I signalling and also prevents fibrosis in other TGF-β-dependent animal models. These findings demonstrate that canonical Wnt signalling is necessary for TGF-β-mediated fibrosis and highlight a key role for the interaction of both pathways in the pathogenesis of fibrotic diseases. © 2012 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2020-07-01

Active visfatin is elevated in serum of maintenance haemodialysis patients and correlates inversely with circulating HDL cholesterol - Nuesken, Kai-Dietrich; Petrasch, Maurice; Rauh, Manfred; Stoehr, Wolfgang; Nuesken, Eva; Schneider, Holm; Dötsch, Jörg (Nephrology Dialysis Transplantation, 2009)
Background. Increased circulating visfatin may be associated both with endothelial damage and with increased mortality in end-stage renal disease (ESRD). HDL cholesterol is an independent, strong inverse predictor of cardiovascular events. However, associations between visfatin and parameters of lipid metabolism are unclear. Moreover, serum concentrations of visfatin measured by an enzyme immuno assay (EIA) are conflicting and do not correlate with ELISA (enzyme-linked immunosorbent assay) data, which predominantly detect enzymatically active visfatin.Methods. A total of 74 haemodialysis (HD) patients and 35 control individuals (C) were studied. All subjects (mean age 62.9 years) provided fasted blood samples (HD patients after 66-69 h without dialysis). Circulating visfatin was measured by the ELISA. Body composition was evaluated using waist circumference, skinfold thickness and body impedance analysis. Results obtained by the ELISA were compared with EIA data.Results. Active serum visfatin was increased in HD (5.58 ± 6.50 ngml) versus C 0.97 ± 1.79 ngml, mean ± SD; P < 0.0001 by multiple regression analysis (MRA) independently of plasma glucose, serum insulin, diabetes, HDL cholesterol and body composition. Within the HD group, only plasma HDL cholesterol (4 lower per additional mgdl HDL; P = 0.001) and insulin-treated diabetes mellitus subgroup of n = 18; 119 higher compared with patients without diabetes (n = 40); P = 0.011 were independently (by MRA) associated with active serum visfatin. Visfatin measured by an EIA showed no correlation with ELISA data.Conclusions. Our study provides reliable data on active visfatin in HD patients using a well-characterized ELISA. Loss of renal function is accompanied by increased circulating active visfatin concentrations in our patients. Furthermore, decreased HDL cholesterol may hint at an increased probability of cardiovascular events in HD patients with elevated serum visfatin.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Body composition; Diabetes; End-stage renal disease; HDL cholesterol; Visfatin

Age-related Differences in Immune Reactions to SARS-CoV-2 Spike and Nucleocapsid Antigens - Morhart, Patrick; Kehl, Sven; Schuh, Wolfgang; Hermes, Katharina; Meltendorf, Stefan; Neubert, Antje; Schneider, Michael; Brunner-Weinzierl, Monika; Schneider, Holm; Lingel, Holger (In Vivo, 2023)
Background/Aim: The manifestation and severity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections show a clear correlation to the age of a patient. The younger a person, the less likely the infection results in significant illness. To explore the immunological characteristics behind this phenomenon, we studied the course of SARS-CoV-2 infections in 11 households, including 8 children and 6 infants/neonates of women who got infected with SARS-CoV-2 during pregnancy. Materials and Methods: We investigated the immune responses of peripheral blood mononuclear cells (PBMCs), umbilical cord blood mononuclear cells (UCBCs), and T cells against spike and nucleocapsid antigens of SARS-COV-2 by flow cytometry and cytokine secretion assays. Results: Upon peptide stimulation, UCBC from neonates showed a strongly reduced IFN-γ production, as well as lower levels of IL-5, IL-13, and TNF-α alongside with decreased frequencies of surface CD137/PD-1 co-expressing CD4+ and CD+8 T cells compared with adult PBMCs. The PBMC response of older children instead was characterized by elevated frequencies of IFN-γ+ CD4+ T cells, but significantly lower levels of multiple cytokines (IL-5, IL-6, IL-9, IL-10, IL-17A, and TNF-α) and a marked shift of the CD4+/CD8+ T-cell ratio towards CD8+ T cells in comparison to adults. Conclusion: The increased severity of SARS-CoV-2 infections in adults could result from the strong cytokine production and lower potential to immunomodulate the excessive inflammation, while the limited IFN-γ production of responding T cells in infants/neonates and the additional higher frequencies of CD8+ T cells in older children may provide advantages during the course of a SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2023-01-13
Keywords: children; COVID-19; immune response; inflammation; neonates; pediatric immunology; SARS-CoV-2; spike protein

ALOX12B and PNPLA1 Have Distinct Roles in Epidermal Lipid Lamellar Organization - Meyer, Jason M.; Vávrová, Kateřina; Radner, Franz P.W.; Schneider, Holm; Dick, Angela; Mauro, Theodora M.; Elias, Peter M. (Journal of Investigative Dermatology, 2022)
CRIS-Team Scopus Importer:2022-12-16

Aloxe3 knockout mice reveal a function of epidermal lipoxygenase-3 as hepoxilin synthase and its pivotal role in barrier formation - Krieg, Peter; Rosenberger, Sabine; De Juanes, Silvia; Latzko, Susanne; Hou, Jin; Dick, Angela; Kloz, Ulrich; Van Der Hoeven, Frank; Hausser, Ingrid; Esposito, Irene; Rauh, Manfred; Schneider, Holm (Journal of Investigative Dermatology, 2013)
Loss-of-function mutations in the lipoxygenase (LOX) genes ALOX12B and ALOXE3 are the second most common cause of autosomal recessive congenital ichthyosis. The encoded proteins, 12R-LOX and epidermal LOX-3 (eLOX-3), act in sequence to convert fatty acid substrates via R-hydroperoxides to specific epoxyalcohol derivatives and have been proposed to operate in the same metabolic pathway during epidermal barrier formation. Here, we show that eLOX-3 deficiency in mice results in early postnatal death, associated with similar but somewhat less severe barrier defects and morphological changes than reported earlier for the 12R-LOX-knockout mice. Skin lipid analysis demonstrated that the severity of barrier failure is related to the loss of covalently bound ceramides in both 12R-LOX- and eLOX-3-null mice, confirming a proposed functional linkage of the LOX pathway to ceramide processing and formation of the corneocyte lipid envelope. Furthermore, analysis of free oxygenated fatty acid metabolites revealed strongly reduced levels of hepoxilin metabolites in eLOX-3-deficient epidermis, indicating an additional function of eLOX-3 in mammalian skin as a hepoxilin synthase linked to the 12S-LOX pathway. © 2013 The Society for Investigative Dermatology.
CRIS-Team Scopus Importer:2020-07-01

A mouse organotypic tissue culture model for autosomal recessive congenital ichthyosis - Rosenberger, S.; Dick, Angela; Latzko, S.; Hausser, I.; Stark, H. -J.; Rauh, Manfred; Schneider, Holm; Krieg, P. (British Journal of Dermatology, 2014)
Autosomal recessive congenital ichthyoses (ARCIs) are keratinization disorders caused by impaired skin barrier function. Mutations in the genes encoding the lipoxygenases 12R-LOX and eLOX-3 are the second most common cause of ARCIs. In recent years, human skin equivalents recapitulating the ARCI phenotype have been established.To develop a murine organotypic tissue culture model for ARCI.Epidermal keratinocytes were isolated from newborn 12R-LOX-deficient mice and cocultivated with mouse dermal fibroblasts embedded in a scaffold of native collagen type I.With this experimental set-up the keratinocytes formed a well-organized multilayered stratified epithelium resembling skin architecture in vivo. All epidermal layers were present and the keratinocytes within showed the characteristic morphological features. Markers for differentiation and maturation indicated regular epidermal morphogenesis. The major components of epidermal structures were expressed, and were obviously processed and assembled properly. In contrast to their wild-type counterparts, 12R-LOX-deficient skin equivalents showed abnormal vesicular structures in the upper epidermal layers correlating with altered lipid composition and increased transepidermal water loss, comparable with 12R-LOX-deficient mice.The mouse skin equivalents faithfully recapitulate the 12R-LOX-deficient phenotype observed in vivo, classifying them as appropriate in vitro models to study molecular mechanisms involved in the development of ARCI and to evaluate novel therapeutic agents. In contrast to existing human three-dimensional skin models, the generation of these murine models is not constrained by a limited supply of material and does not depend on in vitro expansion and/or genetic manipulations that could result in inadvertent genotypic and phenotypic alterations.
EVALuna2:18903

A New Mouse Model of Junctional Epidermolysis Bullosa: The LAMB3 628G > A Knockin Mouse - Hammersen, Johanna; Hou, Jin; Wünsche, Stephanie; Brenner, Sven; Winkler, Thomas; Schneider, Holm (Journal of Investigative Dermatology, 2015)

A novel missense mutation in the gene EDARADD associated with an unusual phenotype of hypohidrotic ectodermal dysplasia - Wohlfart, Sigrun; Söder, Stephan; Smahi, Asma; Schneider, Holm (American Journal of Medical Genetics Part A, 2016)
Hypohidrotic ectodermal dysplasia (HED) is a rare disorder characterized by deficient development of structures derived from the ectoderm including hair, nails, eccrine glands, and teeth. HED forms that are caused by mutations in the genes EDA, EDAR, or EDARADD may show almost identical phenotypes, explained by a common signaling pathway. Proper interaction of the proteins encoded by these three genes is important for the activation of the NF-?B signaling pathway and subsequent transcription of the target genes. Mutations in the gene EDARADD are most rarely implicated in HED. Here we describe a novel missense mutation, c.367G>A (p.Asp123Asn), in this gene which did not appear to influence the interaction between EDAR and EDARADD proteins, but led to an impaired ability to activate NF-?B signaling. Female members of the affected family showed either unilateral or bilateral amazia. In addition, an affected girl developed bilateral ovarian teratomas, possibly associated with her genetic condition.
EVALuna2:6777

A surrogate cell-based SARS-CoV-2 spike blocking assay - Schuh, Wolfgang; Baus, Lena; Steinmetz, Tobit; Schulz, Sebastian; Weckwerth, Leonie; Roth, Edith; Hauke, Manuela; Krause, Stefan; Morhart, Patrick; Rauh, Manfred; Hoffmann, Markus; Vesper, Niklas; et al. (European Journal of Immunology, 2021)
To monitor infection by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and successful vaccination against coronavirus disease 2019 (COVID-19), the kinetics of neutralizing or blocking anti-SARS-CoV-2 antibody titers need to be assessed. Here, we report the development of a quick and inexpensive surrogate SARS-CoV-2 blocking assay (SUBA) using immobilized recombinant human angiotensin-converting enzyme 2 (hACE2) and human cells expressing the native form of surface SARS-CoV-2 spike protein. Spike protein-expressing cells bound to hACE2 in the absence or presence of blocking antibodies were quantified by measuring the optical density of cell-associated crystal violet in a spectrophotometer. The advantages are that SUBA is a fast and inexpensive assay, which does not require biosafety level 2- or 3-approved laboratories. Most importantly, SUBA detects blocking antibodies against the native trimeric cell-bound SARS-CoV-2 spike protein and can be rapidly adjusted to quickly pre-screen already approved therapeutic antibodies or sera from vaccinated individuals for their ACE2 blocking activities against any emerging SARS-CoV-2 variants.
CRIS-Team Scopus Importer:2021-10-08
Keywords: COVID-19; hACE2; SARS-CoV-2; Spike protein; Surrogate blocking assay

Attenuation of Mammary Gland Dysplasia and Feeding Difficulties in Tabby Mice by Fetal Therapy - Wahlbuhl, Mandy; Schuepbach-Mallepell, Sonia; Kowalczyk-Quintas, Christine; Dick, Angela; Fahlbusch, Fabian B.; Schneider, Pascal; Schneider, Holm (Journal of Mammary Gland Biology and Neoplasia, 2018)
Hypohidrotic ectodermal dysplasias (HED) are hereditary differentiation disorders of multiple ectodermal structures including the mammary gland. The X-linked form of HED (XLHED) is caused by a lack of the secreted signaling molecule ectodysplasin A1 (EDA1) which is encoded by the gene EDA and belongs to the tumor necrosis factor (TNF) superfamily. Although male patients (hemizygous) are usually more severely affected by XLHED, heterozygous female carriers of an EDA mutation may also suffer from a variety of symptoms, in particular from abnormal development of their breasts. In Tabby mice, a well-studied animal model of XLHED, EDA1 is absent. We investigated the effects of prenatal administration of Fc-EDA, a recombinant EDA1 replacement protein, on mammary gland development in female Tabby mice. Intra-amniotic delivery of Fc-EDA to fetal animals resulted later in improved breastfeeding and thus promoted the growth of their offspring. In detail, such treatment led to a normalization of the nipple shape (protrusion, tapering) that facilitated sucking. Mammary glands of treated female Tabby mice also showed internal changes, including enhanced branching morphogenesis and ductal elongation. Our findings indicate that EDA receptor stimulation during development has a stable impact on later stages of mammary gland differentiation, including lactation, but also show that intra-amniotic administration of an EDA1 replacement protein to fetal Tabby mice partially corrects the mammary gland phenotype in female adult animals.
EVALuna2:35485

Attenuation of Severe Generalized Junctional Epidermolysis Bullosa by Systemic Treatment with Gentamicin - Hammersen, Johanna; Neuner, Andrea; Wild, Florian; Schneider, Holm (Dermatology, 2019)
Severe generalized junctional epidermolysis bullosa (JEB), a lethal genodermatosis, is mainly caused by premature termination codons (PTCs) in one of the three genes encoding the anchoring protein laminin-332. Only symptomatic treatment has been established; overcoming PTCs by aminoglycosides may represent an interesting alternative. This retrospective study aimed at assessing for the first time the clinical effects of systemic gentamicin application in infants with severe generalized JEB. Five patients, homozygous or compound-heterozygous for PTCs in the gene LAMB3, were treated with gentamicin which was administered intravenously or by intramuscular injection at doses of 7.5 mg/kg/d for three weeks. Skin biopsies were investigated by immunofluorescence analyses. Clinical effects of the medication were recorded with a parent questionnaire and by assessing weight-for-age charts. Gentamicin application was well tolerated, long hospitalization was not required. Low levels of laminin-332 could be detected in a skin sample obtained after treatment. Gentamicin had a positive impact on skin fragility and daily life in four patients but did not influence weight gain and failed to reverse the lethal course of the disease. Gentamicin injections should be considered regularly in cases of severe generalized JEB caused by PTCs as they may attenuate JEB symptoms without impeding quality of life.
CRIS-Team Scopus Importer:2019-06-18

Automatic recognition of the XLHED phenotype from facial images - Hadj-Rabia, Smail; Schneider, Holm; Navarro, Elena; Klein, Ophir; Kirby, Neil; Huttner, Kenneth; Wolf, Lior; Orin, Melanie; Wohlfart, Sigrun; Bodemer, Christine; Grange, Dorothy K. (American Journal of Medical Genetics Part A, 2017)
X-linked hypohidrotic ectodermal dysplasia (XLHED) is a genetic disorder that affects ectodermal structures and presents with a characteristic facial appearance. The ability of automated facial recognition technology to detect the phenotype from images was assessed . In Phase 1 of this study we examined if the age of male patients affected the technology's recognition. In Phase 2 we investigated how well the technology discriminated affected males cases from female carriers and from individuals with other ectodermal dysplasia syndromes. The system detected XLHED to be the most likely diagnosis in all genetically confirmed affected male patients of all ages, and in 55% of heterozygous females. Interestingly, patients with other ED syndromes were also detected by the XLHED-targeted analysis, consistent with shared developmental features. Thus the automated facial recognition system represents a promising non-invasive technology to screen patients at all ages for a possible diagnosis of ectodermal dysplasia, with greatest sensitivity and specificity for males affected with XLHED.
EVALuna2:34218

BAFF 60-mer, and Differential BAFF 60-mer Dissociating Activities in Human Serum, Cord Blood and Cerebrospinal Fluid - Eslami, Mahya; Meinl, Edgar; Eibel, Hermann; Willen, Laure; Donzé, Olivier; Distl, Ottmar; Schneider, Holm; Speiser, Daniel E.; Tsiantoulas, Dimitrios; Yalkinoglu, Ozkan; Samy, Eileen; Schneider, Pascal (Frontiers in Cell and Developmental Biology, 2020)
B cell activation factor of the TNF family (BAFF/BLyS), an essential B cell survival factor of which circulating levels are elevated in several autoimmune disorders, is targeted in the clinic for the treatment of systemic lupus erythematosus (SLE). The soluble form of BAFF can exist as 3-mer, or as 60-mer that results from the ordered assembly of twenty 3-mers and that can be obtained from naturally cleaved membrane-bound BAFF or made as a recombinant protein. However, which forms of soluble BAFF exist and act in humans is unclear. In this study, BAFF 3-mer and 60-mer in biological fluids were characterized for size, activity and response to specific stimulators or inhibitors of BAFF. Human cerebrospinal fluids (CSF) from patients with multiple sclerosis and adult human sera contained exclusively BAFF 3-mer in these assays, also when BAFF concentrations were moderately SLE or highly (BAFFR-deficient individual) increased. Human sera, but not CSF, contained a high molecular weight, saturable activity that dissociated preformed recombinant BAFF 60-mer into 3-mer. This activity was lower in cord blood. Cord blood displayed BAFF levels 10-fold higher than in adults and consistently contained a fair proportion of active high molecular weight BAFF able to dissociate into 3-mer but not endowed with all properties of recombinant BAFF 60-mer. If BAFF 60-mer is produced in humans, it is dissociated, or at least attenuated in the circulation.
CRIS-Team Scopus Importer:2020-11-27
Keywords: 60-mer; atacicept; B-cell activating factor; belimumab; cerebrospinal fluid; cord blood; serum

Beratung nach pränatalen Diagnosen: Sorgen wir für Informationen aus erster Hand! - Schneider, Holm (Zeitschrift für Geburtshilfe und Neonatologie, 2024)

Biallelic KRT5 mutations in autosomal recessive epidermolysis bullosa simplex, including a complete human keratin 5 “knock-out” - Vahidnezhad, Hassan; Youssefian, Leila; Daneshpazhooh, Maryam; Mahmoudi, Hamidreza; Kariminejad, Ariana; Fischer, Judith; Christiansen, Julie; Schneider, Holm; Guy, Alyson; Liu, Lu; McGrath, John A.; Has, Cristina; et al. (Matrix Biology, 2019)
Epidermolysis bullosa simplex (EBS) is usually inherited as an autosomal dominant disease due to monoallelic gain-of-function mutations in KRT5 or KRT14. Although autosomal recessive forms of EBS have been associated with mutations in at least 10 genes, recessive EBS due to homozygous biallelic KRT5 mutations has not been reported previously; it has been hypothesized that it would result in prenatal lethality. We sought the genetic causes of EB in a cohort of 512 distinct EB families by performing whole exome sequencing (WES) and using an EB-targeting next-generation sequencing (NGS) panel of 21 genes. The pathogenicity and consequences of the mutations were determined by expression profiling and at tissue and ultrastructural levels. Two pathogenic, homozygous missense variants of KRT5 in two patients with generalized EBS and a homozygous null mutation in a patient who died as a neonate from complications of EB were found. The two missense mutations disrupted keratin 5 expression on immunofluorescence microscopy, and the human “knock-out” of KRT5 showed no RNA and protein expression. Collectively, these findings identify biallelic KRT5 mutations with a phenotypic spectrum varying from mild, localized and generalized to perinatal lethal, expanding the genotypic profile of autosomal recessive EBS.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Epidermolysis bullosa simplex; KRT5 homozygosity; Next generation sequencing; Phenotype-genotype correlations

Cell-based resurfacing of large cartilage defects: Long-term evaluation of grafts from autologous transgene-activated periosteal cells in a porcine model of osteoarthritis - Gelse, Koja; Muehle, Christiane; Franke, Oliver; Park, Jung; Jehle, Marc; Durst, Karsten; Göken, Mathias; Hennig, Friedrich; Mark, Klaus; Schneider, Holm (Arthritis & Rheumatism-Arthritis Care & Research, 2008)
WW1::753

Conditional Alox12b Knockout: Degradation of the Corneocyte Lipid Envelope in a Mouse Model of Autosomal Recessive Congenital Ichthyoses - Krieg, P.; Dick, Angela; Latzko, Susanne; Rosenberger, Sabine; Meyer, J.; Crumrine, D.; Hielscher, Thomas; Elias, Peter M.; Rauh, Manfred; Schneider, Holm (Journal of Investigative Dermatology, 2019)
CRIS-Team Scopus Importer:2019-09-17

Congenital Nail Disorders among Children with Suspected Ectodermal Dysplasias - Maier-Wohlfart, Sigrun; Aicher, Carmen; Willershausen, Ines; Peschel, Nicolai; Meißner, Udo; Gölz, Lina; Schneider, Holm (Genes, 2022)
We report on a cohort of 204 children referred between January 2017 and January 2022 to the German Center for Ectodermal Dysplasias, Erlangen. The most frequent reasons for referral were tooth malformations and lack of multiple teeth leading to the suspicion of an ectodermal dysplasia. Many patients also suffered from being unable to perspire. Nail abnormalities, in contrast, represented a much rarer finding, albeit the impact on some individuals was large. As ectodermal dysplasias are congenital genetic conditions affecting the development and/or homeostasis of two or more ectodermal derivatives, including hair, teeth, nails, and certain glands, we analyzed congenital nail disorders detected in these patients. Dystrophic or otherwise abnormal nails were evident in 17 of 18 subjects with pathogenic WNT10A or GJB6 variants but in none of 161 children with EDA variants underlying X-linked hypohidrotic ectodermal dysplasia. However, 2 of 17 children who carry mutations in EDAR or EDARADD, two other genes involved in the ectodysplasin A signaling pathway, showed nail abnormalities, such as brittle or hypoplastic nails. TP63 variants were regularly associated with nail disorders. In one girl, anonychia congenita caused by a compound heterozygous variant of the R-spondin-4 gene (RSPO4) was diagnosed. Thus, nail dysplasia is rarer among patients with ectodermal dysplasia than commonly thought.
CRIS-Team Scopus Importer:2022-12-09
Keywords: anonychia/hyponychia congenita; congenital nail disorders; ectodermal dysplasia; R-spondin 4 (RSPO4)

Consider further differential diagnoses - Schneider, Holm (Deutsches Ärzteblatt international, 2014)
EVALuna2:18897

Correction of Vertebral Bone Development in Ectodysplasin A1-Deficient Mice by Prenatal Treatment With a Replacement Protein - Kossel, Clara-Sophie; Wahlbuhl-Becker, Mandy; Schuepbach-Mallepell, Sonia; Park, Jung; Kowalczyk-Quintas, Christine; Seeling, Michaela; von der Mark, Klaus; Schneider, Pascal; Schneider, Holm (Frontiers in Genetics, 2021)
X-linked hypohidrotic ectodermal dysplasia with the cardinal symptoms hypodontia, hypotrichosis and hypohidrosis is caused by a genetic deficiency of ectodysplasin A1 (EDA1). Prenatal EDA1 replacement can rescue the development of skin appendages and teeth. Tabby mice, a natural animal model of EDA1 deficiency, additionally feature a striking kink of the tail, the cause of which has remained unclear. We studied the origin of this phenomenon and its response to prenatal therapy. Alterations in the distal spine could be noticed soon after birth, and kinks were present in all Tabby mice by the age of 4 months. Although their vertebral bones frequently had a disorganized epiphyseal zone possibly predisposing to fractures, cortical bone density was only reduced in vertebrae of older Tabby mice and even increased in their tibiae. Different availability of osteoclasts in the spine, which may affect bone density, was ruled out by osteoclast staining. The absence of hair follicles, a well-known niche of epidermal stem cells, and much lower bromodeoxyuridine uptake in the tail skin of 9-day-old Tabby mice rather suggest the kink being due to a skin proliferation defect that prevents the skin from growing as fast as the skeleton, so that caudal vertebrae may be squeezed and bent by a lack of skin. Early postnatal treatment with EDA1 leading to delayed hair follicle formation attenuated the kink, but did not prevent it. Tabby mice born after prenatal administration of EDA1, however, showed normal tail skin proliferation, no signs of kinking and, interestingly, a normalized vertebral bone density. Thus, our data prove the causal relationship between EDA1 deficiency and kinky tails and indicate that hair follicles are required for murine tail skin to grow fast enough. Disturbed bone development appears to be partially pre-determined in utero and can be counteracted by timely EDA1 replacement, pointing to a role of EDA1 also in osteogenesis.
CRIS-Team Scopus Importer:2021-09-10
Keywords: bone; development; ectodermal dysplasia; ectodysplasin A1; fetal therapy; NF-κB

Cullin 7 and Fbxw 8 expression in trophoblastic cells is regulated via oxygen tension: Implications for intrauterine growth restriction - Fahlbusch, Fabian; Dawood, Yousif Louay; Hartner, Andrea; Menendez-Castro, Carlos; Nögel, Stephanie; Tzschoppe, Anja; Schneider, Holm; Strissel, Pamela; Beckmann, Matthias; Schleussner, Ekkehard; Rübner, Matthias; Dörr, Helmuth-Günther; et al. (Journal of Maternal-Fetal & Neonatal Medicine, 2012)
Objective: The F-box protein Fbxw8 is a cofactor of Cullin 7 (Cul7), which regulates protein transfer to the proteasome and cell growth. Cul7 or Fbxw8 deficiency is associated with intrauterine growth restriction (IUGR) due to abnormal placental development leading to poor oxygen supply to the fetus. We studied the role of hypoxia for Fbxw8 and Cul7 expression in trophoblastic cells. Methods: Immunomagnetic bead-separated extravillous trophoblast (EVT) and villous trophoblast (VT) and trophoblast cell lines were incubated with 1 or 8% O2. Fbxw8 and Cul7 expression was determined in IUGR versus matched control placentas. Results: Fbxw8 was expressed uniformly in trophoblasts, whereas Cul7 expression was most prominent in trophoblast cell lines. Hypoxia reduced expression of Cul7 and Fbxw8 in all trophoblastic cells, except for villous trophoblasts. In vivo, Cul7 and Fbxw8 were detected in syncytiotrophoblast cells, VT, and EVT cells. Although no significant changes in expression levels of Fbxw8 or Cul7 were noted in IUGR compared with control placentas, Fbxw8 expression correlated negatively with gestational age in the control, but not in the IUGR group. Conclusion: Fbxw8 and Cul7 expression reveals a complex regulation in trophoblastic cells. Our findings suggest that dysregulation of Cul7 and Fbxw8 expression might affect trophoblast turnover in IUGR. © 2012 Informa UK, Ltd.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Cul7; Fbxw8; IUGR; Oxygen; Placenta; Trophoblast

Deficiency of Fhl2 leads to delayed neuronal cell migration and premature astrocyte differentiation - Kim, Soung Yung; Ludwig, Stephan; Schneider, Holm; Wixler, Viktor; Park, Jung; Völkl, Simon (Journal of Cell Science, 2019)
The four and a half LIM domains protein 2 (Fhl2) is an adaptor protein capable of mediating protein-protein interactions. Here, we report for the first time phenotypic changes in the brain of Fhl2-deficient mice. We showed that Fhl2 is expressed in neural stem cells, precursors and mature cells of neuronal lineage. Moreover, Fhl2 deficiency leads to delayed neuroblast migration in vivo, premature astroglial differentiation of neural stem cells (NSCs) in vitro, and a gliosis-like accumulation of glial fibrillary acidic protein (GFAP)-positive astrocytes in vivo that substantially increases with age. Collectively, Fhl2-deficiency in the brain interrupts the maintenance and the balanced differentiation of adult NSCs, resulting in preferentially glial differentiation and early exhaustion of the NSC pool required for adult neurogenesis.
CRIS-Team WoS Importer:2019-04-12

Diagnosis of X-Linked Hypohidrotic Ectodermal Dysplasia by Meibography and Infrared Thermography of the Eye - Kärcher, Thomas; Dietz, Jasna; Jacobi, Christina; Berz, Reinhold; Schneider, Holm (Current Eye Research, 2015)
X-linked hypohidrotic ectodermal dysplasia (XLHED) is the most common form of ectodermal dysplasia. Clinical characteristics include meibomian gland disorder and the resulting hyperevaporative dry eye. In this study, we evaluated meibography and ocular infrared thermography as novel methods to diagnose XLHED.Eight infants, 12 boys and 14 male adults with XLHED and 12 healthy control subjects were subjected to a panel of tests including the ocular surface disease index (OSDI), meibography and infrared thermography, non-invasive measurement of tear film break-up time (NIBUT) and osmolarity, Schirmer's test, lissamine green staining and fluorescein staining. Sensitivity and specificity were determined for single tests and selected test combinations.Meibography had 100% sensitivity and specificity for identifying XLHED. Infrared thermography, a completely non-invasive procedure, revealed a typical pattern for male subjects with XLHED. It was, however, less sensitive (86% for adults and 67% for children) than meibography or a combination of established routine tests. In adults, OSDI and NIBUT were the best single routine tests (sensitivity of 86% and 71%, respectively), whereas increased tear osmolarity appeared as a rather unspecific ophthalmic symptom. In children, NIBUT was the most convincing routine test (sensitivity of 91%).Meibography is the most reliable ophthalmic examination to establish a clinical diagnosis in individuals with suspected hypohidrotic ectodermal dysplasia, even before genetic test results are available. Tear film tests and ocular surface staining are less sensitive in children, but very helpful for estimating the severity of ocular surface disease in individuals with known XLHED.
EVALuna2:18886

Digital Workout Versus Team Training: The Impact of the COVID-19 Pandemic on Athletes. - Schneider, Friedemann; Runer, Armin; Burkert, Francesco; Und Aspang, Jesse Seilern; Reider, Simone; Schneider, Holm; Pocecco, Elena (Sports Medicine International Open, 2022)
The aim of the study was to assess the effects of the COVID-19 pandemic on sport practice and to identify measures adopted by individuals and sports organizations to allow a safe return to community sports. An electronic survey was launched worldwide in June 2020 in the German and English languages. The questionnaire collected anonymous data on sporting activity before, during, and after pandemic-induced confinement. Participants classified themselves as either recreational, competitive, or professional sports level athletes. A total of 1336 adults (30.5±11.7 years; 54.0% women) participated in the survey; 68.5% were active athletes, 10.1% coaches, 2.1% officials and 4.3% related medical staff, 3.6% had another function, and 11.4% indicated no regular sports activity. Most participants practiced their sport in Europe (93.8%); the majority (61.0%) was amateur athletes. During confinement, 15.7% could perform their main sport unrestricted, 43.5% stated a reduced amount of time spent on sporting activities, 46.4% a reduced intensity level. Most participants (77.5%) were neither aware of screening measures nor of guidelines for dealing with infected athletes (80.0%) or for return to sports after a coronavirus infection (88.6%). Preventive measures mentioned included basic hygiene, measures to reduce personal contacts or virus transmission, or to improve traceability of infections. During confinement, a higher age (p=0.004) and training in a club setting (p<0.001) were associated with reduced sporting activity, while the availability of online training (p=0.030 ) was linked to both increased extent and intensity levels. A lower age (p=0.001) and recreational sports level (p=0.005) were associated with decreased activity after confinement. Although isolation can be necessary to protect public health, it alters the amount and intensity of physical activity.
EVALuna2:514670

Diminished protein-bound ω-hydroxylated ceramides in the skin of patients with ichthyosis with 12R-lipoxygenase (LOX) or eLOX-3 deficiency - Dick, A.; Tantcheva-Poor, I. .; Oji, V.; Giehl, K. A.; Fischer, J. .; Krieg, P.; Schneider, Holm; Rauh, Manfred (British Journal of Dermatology, 2017)
EVALuna2:34217

Dual pathways to endochondral osteoblasts: a novel chondrocyte-derived osteoprogenitor cell identified in hypertrophic cartilage - Park, Jung; Gebhardt, Matthias; Golovchenko, Svitlana; Perez-Branguli, Francesc; Hattori, Takako; Hartmann, Christine; Zhou, Xin; Decrombrugghe, Benoit; Stock, Michael; Schneider, Holm; Mark, Klaus (Biology Open, 2015)
According to the general understanding, the chondrocyte lineage terminates with the elimination of late hypertrophic cells by apoptosis in the growth plate. However, recent cell tracking studies have shown that murine hypertrophic chondrocytes can survive beyond "terminal" differentiation and give rise to a progeny of osteoblasts participating in endochondral bone formation. The question how chondrocytes convert into osteoblasts, however, remained open. Following the cell fate of hypertrophic chondrocytes by genetic lineage tracing using BACCol10;Cre induced YFP-reporter gene expression we show that a progeny of Col10Cre-reporter labelled osteoprogenitor cells and osteoblasts appears in the primary spongiosa and participates - depending on the developmental stage - substantially in trabecular, endosteal, and cortical bone formation. YFP(+) trabecular and endosteal cells isolated by FACS expressed Col1a1, osteocalcin and runx2, thus confirming their osteogenic phenotype. In searching for transitory cells between hypertrophic chondrocytes and trabecular osteoblasts we identified by confocal microscopy a novel, small YFP(+)Osx(+) cell type with mitotic activity in the lower hypertrophic zone at the chondro-osseous junction. When isolated from growth plates by fractional enzymatic digestion, these cells termed CDOP (chondrocyte-derived osteoprogenitor) cells expressed bone typical genes and differentiated into osteoblasts in vitro. We propose the Col10Cre-labeled CDOP cells mark the initiation point of a second pathway giving rise to endochondral osteoblasts, alternative to perichondrium derived osteoprogenitor cells. These findings add to current concepts of chondrocyte-osteocyte lineages and give new insight into the complex cartilage-bone transition process in the growth plate.
EVALuna2:10200

Ectodermal dysplasias: Classification and organization by phenotype, genotype and molecular pathway - Wright, John Timothy; Fete, Mary; Schneider, Holm; Zinser, Madelaine; Koster, Maranke I.; Clarke, Angus J.; Hadj-Rabia, Smail; Tadini, Gianluca; Pagnan, Nina; Visinoni, Atila F.; Bergendal, Birgitta; Abbott, Becky; et al. (American Journal of Medical Genetics Part A, 2019)
An international advisory group met at the National Institutes of Health in Bethesda, Maryland in 2017, to discuss a new classification system for the ectodermal dysplasias (EDs) that would integrate both clinical and molecular information. We propose the following, a working definition of the EDs building on previous classification systems and incorporating current approaches to diagnosis: EDs are genetic conditions affecting the development and/or homeostasis of two or more ectodermal derivatives, including hair, teeth, nails, and certain glands. Genetic variations in genes known to be associated with EDs that affect only one derivative of the ectoderm (attenuated phenotype) will be grouped as non-syndromic traits of the causative gene (e.g., non-syndromic hypodontia or missing teeth associated with pathogenic variants of EDA "ectodysplasin"). Information for categorization and cataloging includes the phenotypic features, Online Mendelian Inheritance in Man number, mode of inheritance, genetic alteration, major developmental pathways involved (e.g., EDA, WNT "wingless-type," TP63 "tumor protein p63") or the components of complex molecular structures (e.g., connexins, keratins, cadherins).
CRIS-Team WoS Importer:2019-02-27

Ectodermal dysplasias: New perspectives on the treatment of so far immedicable genetic disorders - Schneider, Holm (Frontiers in Genetics, 2022)
The past decade has witnessed an expansion of molecular approaches facilitating the differential diagnosis of ectodermal dysplasias, a group of genetic diseases characterized by the lack or malformation of hair, teeth, nails, and certain eccrine glands. Moreover, advances in translational research have increased the therapeutic opportunities for such rare diseases, and new dental, surgical, and ophthalmic treatment options are likely to offer relief to many individuals affected by ectodermal dysplasias. In X-linked hypohidrotic ectodermal dysplasia (XLHED), the genetic deficiency of the signaling molecule ectodysplasin A1 (EDA1) may even be overcome before birth by administration of a recombinant replacement protein. This has been shown at least for the key problem of male subjects with XLHED, the nearly complete absence of sweat glands and perspiration which can lead to life-threatening hyperthermia. Prenatal treatment of six boys by injection of an EDA1 replacement protein into the amniotic fluid consistently induced the development of functional sweat glands. Normal ability to sweat has so far persisted for > 5 years in the two oldest boys treated in utero. Thus, timely replacement of a missing protein appears to be a promising therapeutic strategy for the most frequent ectodermal dysplasia and possibly additional congenital disorders.
CRIS-Team WoS Importer:2022-09-30

Ectodysplasin A1 Deficiency Leads to Osteopetrosis-like Changes in Bones of the Skull Associated with Diminished Osteoclastic Activity - Schweikl, Christine; Maier-Wohlfart, Sigrun; Schneider, Holm; Park, Jung (International Journal of Molecular Sciences, 2022)
Pathogenic variants of the gene Eda cause X-linked hypohidrotic ectodermal dysplasia (XLHED), which is characterized by structural abnormalities or lack of ectodermal appendages. Signs of dysplasia are not restricted to derivatives of the ectodermal layer, but mesodermal abnormalities, such as craniofacial dysmorphism, are also frequently observed, suggesting close reciprocal interactions between the ectoderm and mesoderm; however, a causal link has remained unsubstantiated. We investigated the functional impact of defective ectodysplasin A1 (Eda1) signaling on postnatal bone homeostasis in Eda1-deficient Tabby mice. Interestingly, Eda1 was detected in wild-type mouse calvariae throughout postnatal lifetime. In calvariae, bone-lining Osterix (Osx)+ osteoblasts stained positive for Eda1, and osteoclasts were revealed as Eda receptor (Edar)-positive. Moreover, adult Eda1-deficient calvarial bone showed osteopetrosis-like changes with significantly diminished marrow space, which was maintained during adulthood. Concomitantly with osteopetrosis-like changes, Tabby calvarial bone and Tabby bone marrow-derived osteoclasts had far less osteoclastic activity-associated co-enzymes including cathepsin K, Mmp9, Trap, and Tcirg1 (V-type proton ATPase a3 subunit) compared with wild-type calvariae in vivo or osteoclasts in vitro, indicating that Eda1 deficiency may affect the activity of osteoclasts. Finally, we confirmed that nuclear Nfatc1-positive osteoclasts were strongly diminished during mature osteoclastic differentiation under M-CSF and RANKL in the Tabby model, while Fc-EDA treatment of Tabby-derived osteoclasts significantly increased nuclear translocation of Nfatc1. Furthermore, we identified enhanced Nfatc1 and NF-κB transcriptional activity following Fc-EDA treatment in vitro using luciferase assays. Overall, the results indicate that diminished expressions of osteoclastic activity-associated co-enzymes may lead to disturbed bone homeostasis in Tabby calvariae postnatally.
CRIS-Team Scopus Importer:2022-11-04
Keywords: bone; ectodermal dysplasia; ectodysplasin A1; NF-κB; NFAT; osteoclast differentiation; osteopetrosis

Ectodysplasin A in Biological Fluids and Diagnosis of Ectodermal Dysplasia - Podzus, J.; Kowalczyk-Quintas, C.; Schuepbach-Mallepell, S.; Willen, L.; Staehlin, G.; Vigolo, M.; Tardivel, A.; Headon, D.; Kirby, N.; Mikkola, M. L.; Schneider, Holm; Schneider, P. (Journal of Dental Research, 2017)
The tumor necrosis factor (TNF) family ligand ectodysplasin A (EDA) is produced as 2 full-length splice variants, EDA1 and EDA2, that bind to EDA receptor (EDAR) and X-linked EDA receptor (XEDAR/EDA2R), respectively. Inactivating mutations in Eda or Edar cause hypohidrotic ectodermal dysplasia (HED), a condition characterized by malformations of the teeth, hair and glands, with milder deficiencies affecting only the teeth. EDA acts early during the development of ectodermal appendages-as early as the embryonic placode stage-and plays a role in adult appendage function. In this study, the authors measured EDA in serum, saliva and dried blood spots. The authors detected 3- to 4-fold higher levels of circulating EDA in cord blood than in adult sera. A receptor binding-competent form of EDA1 was the main form of EDA but a minor fraction of EDA2 was also found in fetal bovine serum. Sera of EDA-deficient patients contained either background EDA levels or low levels of EDA that could not bind to recombinant EDAR. The serum of a patient with a V262F missense mutation in Eda, which caused a milder form of X-linked HED (XLHED), contained low levels of EDA capable of binding to EDAR. In 2 mildly affected carriers, intermediate levels of EDA were detected, whereas a severely affected carrier had no active EDA in the serum. Small amounts of EDA were also detectable in normal adult saliva. Finally, EDA could be measured in spots of wild-type adult or cord blood dried onto filter paper at levels significantly higher than that measured in EDA-deficient blood. Measurement of EDA levels combined with receptor-binding assays might be of relevance to aid in the diagnosis of total or partial EDA deficiencies.
EVALuna2:34220

Editorial: Gene, Cell and Protein Replacement Therapy for Genetic Muscle, Bone and Skin Disorders - Schneider, Holm; De Luca, Michele (Frontiers in Genetics, 2021)
CRIS-Team Scopus Importer:2021-11-12
Keywords: duchenne muscular dystrophy (DMD); ectodermal dysplasia; epidermolysis bullosa; gene therapy; myogenic cell transplantation; protein replacement

Efficiency of translation termination in humans is highly dependent upon nucleotides in the neighbourhood of a (premature) termination codon - Pacho, Frederic; Zambruno, Giovanna; Calabresi, Valentina; Kiritsi, Dimitra; Schneider, Holm (Journal of Medical Genetics, 2011)
Background Spontaneous read-through of a premature termination codon (PTC) has so far not been observed in patients carrying nonsense mutations. This report describes a patient with junctional epidermolysis bullosa who was expected to die because of compound heterozygous nonsense mutations in the gene LAMA3 (R943X/R1159X), but was rescued by spontaneous readthrough of the R943X allele. Results and conclusion FACS analysis of cells carrying various PTCs surrounded by their natural neighbouring codons revealed significant reporter gene expression despite the PTC only for this patient's genetic context. Gene expression could be abolished by replacing the first or third nucleotide before, or one of the two nucleotides following the PTC. Site-directed mutagenesis was used to identify genotypes allowing PTC read-through. The genetic context of the LAMA3 mutation R943X is close to a hypothetical consensus sequence for maximum PTC read-through. Bioinformatic analysis showed that this consensus sequence is present in four sequences from the NCBI reference database, each of which contains another in-frame termination codon three or four codons apart. This indicates strong selective pressure against leaky termination codons in the human genome. This patient's mutated full length mRNA escaped nonsensemediated decay, leading to LAMA3 mRNA levels similar to those of a healthy control, and full length laminin a3 could be detected in culture supernatant of the patient's keratinocytes. Immunofluorescence analyses of skin biopsies and continuous clinical improvement of the patient's condition suggested accumulation of intact laminin-332 in the epidermal basement membrane. These findings provide important clues for the prediction of PTC read-through in human genetic disease.
CRIS-Team Scopus Importer:2020-07-01

Electric Field-Induced Osteogenic Differentiation on TiO2 Nanotubular Layer - Park, Jung Hyun; Mazare, Anca Valentina; Schneider, Holm; Mark, Klaus; Fischer, Michael; Schmuki, Patrik (Tissue Engineering - Part C: Methods, 2016)
On biocompatible implant surfaces, cellular behavior and fate of stem cells are determined not only by microenvironmental signals but also by electrochemical signals. The potential of electric fields (EFs) to stimulate bone growth and bone healing has been widely demonstrated, but the molecular mechanism linking EFs to osteogenic differentiation has remained elusive. Here we show that constant EFs triggered osteogenic induction of mesenchymal stem cells (MSCs) on a defined nanotubular TiO2 substrate. EFs stimulate the formation of plasma membrane protrusions and the transport of connexin 43 to these protrusions. Connexin 43 is required for the EF-induced lasting intracellular calcium increase, which rapidly propagates to neighboring cells by gap junctions. This enables simultaneous osteogenic induction following downstream calcineurin/CAMKII/NFAT signaling. We propose that connexin 43-mediated, EF-induced osteogenic differentiation of MSCs on a defined nanotubular titanium oxide surface may give new insight on therapeutic interventions for bone regeneration and tissue engineering approaches.
EVALuna2:10221

ENGRAFTMENT, DIFFERENTIATION AND BIOLOGICAL EFFECTS OF CORD BLOOD-DERIVED CLONAL CELLS ADMINISTERED INTRAVENOUSLY TO NEWBORN RATS WITH HYPOXIC-ISCHEMIC BRAIN INJURY - Yang, Xiaojun; Griesmaier, E.; Wegleiter, K.; Schlager, G. W.; Weisbach, Volker Günter; Keller, M.; Park, J.; Schneider, Holm (2016)
EVALuna2:34012

Epidemiology of inherited epidermolysis bullosa in Germany - Has, Cristina; Hess, Moritz; Anemueller, Waltraud; Blume-Peytavi, Ulrike; Emmert, Steffen; Foelster-Holst, Regina; Frank, Jorge; Giehl, Kathrin; Guenther, Claudia; Hammersen, Johanna; Hillmann, Kathrin; Hoeflein, Bettina; et al. (Journal of the European Academy of Dermatology and Venereology, 2022)
Background Epidermolysis bullosa (EB) is a rare genetic disorder manifesting with skin and mucosal membrane blistering in different degrees of severity. Objective Epidemiological data from different countries have been published, but none are available from Germany. Methods In this population-based cross-sectional study, people living with EB in Germany were identified using the following sources: academic hospitals, diagnostic laboratories and patient organization. Results Our study indicates an overall EB incidence of 45 per million live births in Germany. With 14.23 per million live births for junctional EB, the incidence is higher than in other countries, possibly reflecting the availability of early molecular genetic diagnostics in severely affected neonates. Dystrophic EB was assessed at 15.58 cases per million live births. The relatively low incidence found for EB simplex, 14.93 per million live births, could be explained by late or missed diagnosis, but also by 33% of cases remaining not otherwise specified. Using log-linear models, we estimated a prevalence of 54 per million for all EB types, 2.44 for junctional EB, 12.16 for dystrophic EB and 28.44 per million for EB simplex. These figures are comparable to previously reported data from other countries. Conclusions Altogether, there are at least 2000 patients with EB in the German population. These results should support national policies and pharmaceutical companies in decision-making, allow more precise planning of drug development and clinical trials, and aid patient advocacy groups in their effort to improve quality of life of people with this orphan disease.
CRIS-Team WoS Importer:2022-11-11

Epidemiology of inherited Epidermolysis bullosa in Germany - Has, Cristina; Hess, Moritz; Anemueller, Waltraud; Blume-Peytavi, Ulrike; Emmert, Steffen; Foelster-Holst, Regina; Frank, Jorge; Giehl, Kathrin; Günther, Claudia; Hammersen, Johanna; Hillmann, Kathrin; Hoeflein, Bettina; et al. (Journal of the European Academy of Dermatology and Venereology, 2023)

Erythroderma and Hypernatraemic Dehydration in Newborn - A Case report of Netherton Syndrome - Anneser, Verena; Mueller, Fabian; Wild, Florian; Metze, Dieter; Schneider, Holm; Steinhoff, Martin; Seeliger, Stephan (Klinische Pädiatrie, 2020)
Netherton syndrome (NS) is a rare, severe, autosomal recessive form of congenital ichthyosis, associated with a characteristic defect in the hair shaft (Trichorrhexis invaginata), erythroderma, and a pronounced atopic disposition due to an altered immune system. Its incidence is about 1:100,000 to 1: 200,000. The disease is caused by mutations in the gene SPINK5 (5q31-q32) which codes for the serine protease inhibitor LEKTI. Affected newborns show a non-uniform picture of generalized erythroderma with scaling of the skin and sometimes even present as Collodion babys. A serious complication during early infancy is hypernatremic dehydration resulting from the inadequate barrier function of the skin. The mucocutaneous barrier dysfunction also leads to recurrent infections, atopy, diarrhea, and intestinal malabsorption with concomitant failure to thrive.
CRIS-Team WoS Importer:2020-06-05

Fetal and Maternal Safety Considerations for In Utero Therapy Clinical Trials: iFeTiS Consensus Statement - Sagar, Rachel; Almeida-Porada, Graça; Blakemore, Karin; Chan, Jerry K.Y.; Choolani, Mahesh; Götherström, Cecilia; Jaulent, Agnes; MacKenzie, Tippi C.; Mattar, Citra; Porada, Christopher D.; Peranteau, William H.; Schneider, Holm; et al. (Molecular Therapy, 2020)
CRIS-Team Scopus Importer:2020-11-06
Keywords: adverse event; clinical trial; fetal; fetal therapy; In utero stem cell transplantation; maternal; safety

Fetal programming of gene expression in growth-restricted rats depends on the cause of low birth weight - Nuesken, Kai-Dietrich; Schneider, Holm; Plank, Christian Georg; Trollmann, Regina; Nuesken, Eva; Rascher, Wolfgang; Doetsch, Joerg (Endocrinology, 2011)
Low birth weight and intrauterine growth restriction (IUGR) can be caused by numerous different conditions. In many experimental settings, however, these different causes are not accounted for. This study aimed at comparing the impact of two frequent causes of IUGR (low utero-placental blood flow vs. malnutrition) on fetal programming of gene expression. We studied offspring of dams treated by uterine artery ligation or sham operation compared with untreated controls and offspring of dams that were fed either a low protein or normal protein diet. After Cesarean section at term, placental and fetal hepatic expression of key "metabolic" and "vasoregulative" genes was investigated by quantitative RT-PCR. Ligation neonates showed IUGR, reduced expression of placental leptin, placental and hepatic IGF-I, hepatic inducible nitric oxide synthase, and increased expression of placental IGF binding protein 1, hepatic IGF-II receptor and erythropoietin (EPO).Low protein offspring also showed IUGR but increased expression of placental leptin; IGF-I; placental and hepatic inducible nitric oxide synthase; hepatic insulin, IGF-I, and IGF-II receptors; and reduced expression of placental IGF binding protein 1, IGF-II, leptin-receptor type A, placental and hepatic leptin receptor type B, and EPO. Expression was independent of sex, birth weight, fetal intrauterine position, and EPO expression. In conclusion, the impact of IUGR on fetal and placental gene expression depends on the cause of low birth weight. Therefore, morbidity after IUGR should be analyzed referring to its pathophysiological cause rather than referring to low birth weight itself. Fetal hypoxia as estimated by hepatic EPO expression does not seem to be a key regulator of transcriptional activity in our models. Copyright © 2011 by The Endocrine Society.
CRIS-Team Scopus Importer:2020-07-01

Functional and clinical analysis of five EDA variants associated with ectodermal dysplasia but with a hard-to-predict significance - Goekdere, Sare; Schneider, Holm; Hehr, Ute; Willen, Laure; Schneider, Pascal; Maier-Wohlfart, Sigrun (Frontiers in Genetics, 2022)
Deficiency of ectodysplasin A1 (EDA1) due to variants of the gene EDA causes X-linked hypohidrotic ectodermal dysplasia (XLHED), a rare genetic condition characterized by abnormal development of ectodermal structures. XLHED is defined by the triad of hypotrichosis, hypo- or anhidrosis, and hypo- or anodontia. Anhidrosis may lead to life-threatening hyperthermia. A definite genetic diagnosis is, thus, important for the patients' management and amenability to a novel prenatal treatment option. Here, we describe five familial EDA variants segregating with the disease in three families, for which different prediction tools yielded discordant results with respect to their significance. Functional properties in vitro and levels of circulating serum EDA were compared with phenotypic data on skin, hair, eyes, teeth, and sweat glands. EDA1-Gly176Val, although associated with relevant hypohidrosis, still bound to the EDA receptor (EDAR). Subjects with EDA1-Pro389LeufsX27, -Ter392GlnfsX30, -Ser125Cys, and an EDA1 splice variant (c.924+7A > G) showed complete absence of pilocarpine-induced sweating. EDA1-Pro389LeufsX27 was incapable of binding to EDAR and undetectable in serum. EDA1-Ter392GlnfsX30, produced in much lower amounts than wild-type EDA1, could still bind to EDAR, and so did EDA1-Ser125Cys that was, however, undetectable in serum. The EDA splice variant c.924+7A > G resulted experimentally in a mix of wild-type EDA1 and EDA molecules truncated in the middle of the receptor-binding domain, with reduced EDA serum concentration. Thus, in vitro assays reflected the clinical phenotype in two of these difficult cases, but underestimated it in three others. Absence of circulating EDA seems to predict the full-blown phenotype of XLHED, while residual EDA levels may also be found in anhidrotic patients. This indicates that unborn subjects carrying variants of uncertain significance could benefit from an upcoming prenatal medical treatment even if circulating EDA levels or tests in vitro suggest residual EDA1 activity.
CRIS-Team WoS Importer:2022-08-12

Generation and characterization of function-blocking anti-ectodysplasin A (EDA) monoclonal antibodies that induce ectodermal dysplasia - Kowalczyk-Quintas, Christine; Willen, Laure; Anh Thu Dang; Sarrasin, Heidi; Tardivel, Aubry; Hermes, Katharina; Schneider, Holm; Gaide, Olivier; Donze, Olivier; Kirby, Neil; Headon, Denis J.; Schneider, Pascal (Journal of Biological Chemistry, 2014)
Development of ectodermal appendages, such as hair, teeth, sweat glands, sebaceous glands, and mammary glands, requires the action of the TNF family ligand ectodysplasin A (EDA). Mutations of the X-linked EDA gene cause reduction or absence of many ectodermal appendages and have been identified as a cause of ectodermal dysplasia in humans, mice, dogs, and cattle. We have generated blocking antibodies, raised in Eda-deficient mice, against the conserved, receptor-binding domain of EDA. These antibodies recognize epitopes overlapping the receptor-binding site and prevent EDA from binding and activating EDAR at close to stoichiometric ratios in in vitro binding and activity assays. The antibodies block EDA1 and EDA2 of both mammalian and avian origin and, in vivo, suppress the ability of recombinant Fc-EDA1 to rescue ectodermal dysplasia in Eda-deficient Tabby mice. Moreover, administration of EDA blocking antibodies to pregnant wild type mice induced in developing wild type fetuses a marked and permanent ectodermal dysplasia. These function-blocking anti-EDA antibodies with wide cross-species reactivity will enable study of the developmental and postdevelopmental roles of EDA in a variety of organisms and open the route to therapeutic intervention in conditions in which EDA may be implicated.
EVALuna2:18884

Genotype, Clinical Course, and Therapeutic Decision Making in 76 Infants with Severe Generalized Junctional Epidermolysis Bullosa - Hammersen, Johanna; Has, Cristina; Naumann-Bartsch, Nora; Stachel, Daniel; Kiritsi, Dimitra; Söder, Stephan; Tardieu, Mathilde; Metzler, Markus; Bruckner-Tuderman, Leena; Schneider, Holm (Journal of Investigative Dermatology, 2016)
Severe generalized junctional epidermolysis bullosa, a lethal hereditary blistering disorder, is usually treated by palliative care. Allogeneic stem cell transplantation (SCT) has been proposed as a therapeutic approach, yet without clinical evidence. Decision making was evaluated retrospectively in 76 patients with severe generalized junctional epidermolysis bullosa born in the years 2000-2015. The diagnosis was based on the absence of laminin-332 in skin biopsies. With an incidence of 1 of 150,000, severe generalized junctional epidermolysis bullosa occurred more often than published previously. Eleven as yet unreported mutations in the laminin-332 genes were detected. Although patients homozygous for the LAMB3 mutation c.1903C>T lived longer than the others, life expectancy was greatly diminished (10.8 vs. 4.6 months). Most patients failed to thrive. In two patients with initially normal weight gain, the decision for SCT from haploidentical bone marrow or peripheral blood was made. Despite transiently increasing skin erosions, the clinical status of both subjects stabilized for several weeks after SCT, but finally deteriorated. Graft cells, but no laminin-332, were detected in skin biopsies. The patients died 96 and 129 days after SCT, respectively, one of them after receiving additional skin grafts. Treatment of severe generalized junctional epidermolysis bullosa by SCT is a last-ditch attempt still lacking proof of efficacy.
EVALuna2:6828

Genotype-phenotype correlation in boys with X-linked hypohidrotic ectodermal dysplasia - Burger, Kristin; Schneider, Anne-Theres; Wohlfart, Sigrun; Kiesewetter, Franklin; Huttner, Kenneth; Johnson, Ramsey; Schneider, Holm (American Journal of Medical Genetics Part A, 2014)
X-linked hypohidrotic ectodermal dysplasia (XLHED), the most frequent form of ectodermal dysplasia, is a genetic disorder of ectoderm development characterized by malformation of multiple ectodermal structures such as skin, hair, sweat and sebaceous glands, and teeth. The disease is caused by a broad spectrum of mutations in the gene EDA. Although XLHED symptoms show inter-familial and intra-familial variability, genotype-phenotype correlation has been demonstrated with respect to sweat gland function. In this study, we investigated to which extent the EDA genotype correlates with the severity of XLHED-related skin and hair signs. Nineteen male children with XLHED (age range 3-14 years) and seven controls (aged 6-14 years) were examined by confocal microscopy of the skin, quantification of pilocarpine-induced sweating, semi-quantitative evaluation of full facial photographs with respect to XLHED-related skin issues, and phototrichogram analysis. All eight boys with known hypomorphic EDA mutations were able to produce at least some sweat and showed less severe cutaneous signs of XLHED than the anhidrotic XLHED patients (e.g., perioral and periorbital eczema or hyperpigmentation, regional hyperkeratosis, characteristic wrinkles under the eyes). As expected, individuals with XLHED had significantly less and thinner hair than healthy controls. However, there were also significant differences in hair number, diameter, and other hair characteristics between the group with hypomorphic EDA mutations and the anhidrotic patients. In summary, this study indicated a remarkable genotype-phenotype correlation of skin and hair findings in prepubescent males with XLHED.
EVALuna2:18885

Hologene 5: A Phase II/III Clinical Trial of Combined Cell and Gene Therapy of Junctional Epidermolysis Bullosa - De Rosa, Laura; Enzo, Elena; Zardi, Giulia; Bodemer, Christine; Magnoni, Cristina; Schneider, Holm; De Luca, Michele (Frontiers in Genetics, 2021)
Epidermolysis bullosa (EB) is a group of devastating genetic diseases characterized by skin and mucosal fragility and formation of blisters, which develop either spontaneously or in response to minor mechanical trauma. There is no definitive therapy for any form of EB. Intermediate junctional EB (JEB) caused by mutations in the gene LAMB3 has been the first genetic skin disease successfully tackled by ex vivo gene therapy. Here, we present a multicenter, open-label, uncontrolled phase II/III study that aims at confirming the efficacy of Hologene 5, a graft consisting of cultured transgenic keratinocytes and epidermal stem cells and meant to combine cell and gene therapy for the treatment of LAMB3-related JEB. Autologous clonogenic keratinocytes will be isolated from patients’ skin biopsies, genetically corrected with a gamma-retroviral vector (γRV) carrying the full-length human LAMB3 cDNA and plated onto a fibrin support (144cm2). The transgenic epidermis will be transplanted onto surgically prepared selected skin areas of at least six JEB patients (four pediatric and two adults). Evaluation of clinical efficacy will include, as primary endpoint, a combination of clinical parameters, such as percentage of re-epithelialization, cellular, molecular, and functional parameters, mechanical stress tests, and patient-reported outcome (PRO), up to 12months after transplantation. Safety and further efficacy endpoints will also be assessed during the clinical trial and for additional 15years in an interventional non-pharmacological follow-up study. If successful, this clinical trial would provide a therapeutic option for skin lesions of JEB patients with LAMB3 mutations and pave the way to a combined cell and gene therapy platform tackling other forms of EB and different genodermatoses. Clinical Trial Registration: EudraCT Number: 2018-000261-36.
CRIS-Team Scopus Importer:2021-10-01
Keywords: cell and gene therapy; clinical trial; epidermal stem cell; epidermolysis bullosa; genodermatoses; skin

Homozygous Biallelic KRT5 Mutations in Epidermolysis Bullosa Simplex, Including a Complete Human Keratin 5 "Knock-Out", in Families with Extensive Consanguinity - Vahidnezhad, H.; Youssefian, L.; Daneshpazhooh, M.; Mahmoudi, H.; Kariminejad, A.; Fischer, J.; Christiansen, J.; Schneider, Holm; Guy, A.; Liu, L.; Mcgrath, J. A.; Has, C.; et al. (JOURNAL OF INVESTIGATIVE DERMATOLOGY, 2019)
CRIS-Team WoS Importer:2019-09-27

Hypohidrotic Ectodermal Dysplasia: Breastfeeding Complications Due to Impaired Breast Development - Wahlbuhl-Becker, Mandy; Faschingbauer, Florian; Beckmann, Matthias; Schneider, Holm (Geburtshilfe und Frauenheilkunde, 2017)
Background X-linked hypohidrotic ectodermal dysplasia (XLHED), the most common form of ectodermal dysplasia, is caused by mutations in the gene EDA. While only affected men develop the full-blown clinical picture, females who are heterozygous for an EDA mutation often also show symptoms such as hypodontia, hypotrichosis and hypohidrosis. These women may also suffer from malformations of the mammary gland which represent not just a cosmetic problem but can limit their breastfeeding capability. This paper summarizes the findings of the first systematic study on the impact of hypohidrotic ectodermal dysplasia on breastfeeding. Patients Thirty-eight adult female members of the German-Swiss-Austrian ectodermal dysplasia patient support group participated in a structured interview; most of them also agreed to a photodocumentation of their mammary region. Thirty-one women carried mutations in EDA (Group A) and seven were affected by other forms of hypohidrotic ectodermal dysplasia (Group B). Results 39 % of the women of Group A reported that their breasts were of different size or entirely absent on one side. In Group B, 86 % of the women reported differently sized or even absent breasts; two of these women lacked both breasts entirely. Most women described their nipples as exceptionally flat. 10 % of the women of Group A had more than two nipples. The high percentage of deviations from the norm was confirmed in the photodocumentation. Both groups had few or no sebaceous glands of Montgomery in the areolar region. Around 80 % of interviewed women had children and had attempted to breastfeed their first child. 67 % of the mothers in Group A had had difficulty in breastfeeding their infants and generally attributed this difficulty to their flat nipples. All of the mothers in Group B reported difficulties in breastfeeding; 60 % had not been able to breastfeed their first child. Conclusion Mothers with hypohidrotic ectodermal dysplasia very often have difficulty in breastfeeding because of their impaired breast development. This causal relationship needs to be taken into account in lactation counseling.
EVALuna2:34219

Increased Rat Placental Fatty Acid, but Decreased Amino Acid and Glucose Transporters Potentially Modify Intrauterine Programming - Nuesken, Eva; Gellhaus, Alexandra; Kuehnel, Elisabeth; Swoboda, Isabelle; Wohlfarth, Maria; Vohlen, Christina; Schneider, Holm; Doetsch, Joerg; Nuesken, Kai-Dietrich (Journal of Cellular Biochemistry, 2016)
Regulation of placental nutrient transport significantly affects fetal development and may modify intrauterine growth restriction (IUGR) and fetal programming. We hypothesized that placental nutrient transporters are differentially affected both by utero-placental insufficiency and prenatal surgical stress. Pregnant rats underwent bilateral uterine artery and vein ligation (LIG), sham operation (SOP) or no operation (controls, C) on gestational day E19. Placentas were obtained by caesarean section 4 h (LIG, n=20 placentas; SOP, n=24; C, n=12), 24 h (LIG, n=28; SOP, n=20; C, n=12) and 72 h (LIG, n=20; SOP, n=20; C, n=24) after surgery. Gene and protein expression of placental nutrient transporters for fatty acids (h-FABP, CD36), amino acids (SNAT1, SNAT2) and glucose (GLUT-1, Connexin 26) were examined by qRT-PCR, western blot and immunohistochemistry. Interestingly, the mean protein expression of h-FABP was doubled in placentas of LIG and SOP animals 4, 24 (SOP significant) and 72 h (SOP significant) after surgery. CD36 protein was significantly increased in LIG after 72 h. SNAT1 and SNAT2 protein and gene expressions were significantly reduced in LIG and SOP after 24 h. Further significantly reduced proteins were GLUT-1 in LIG (4 h, 72 h) and SOP (24 h), and Connexin 26 in LIG (72 h). In conclusion, placental nutrient transporters are differentially affected both by reduced blood flow and stress, probably modifying the already disturbed intrauterine milieu and contributing to IUGR and fetal programming. Increased fatty acid transport capacity may affect energy metabolism and could be a compensatory reaction with positive effects on brain development. J. Cell. Biochem. 117: 1594-1603, 2016. © 2015 Wiley Periodicals, Inc.
EVALuna2:33879

Increased risk of chronic fatigue and hair loss following COVID-19 in individuals with hypohidrotic ectodermal dysplasia - Hennig, Verena; Schuh, Wolfgang; Neubert, Antje; Mielenz, Dirk; Jäck, Hans-Martin; Schneider, Holm (Orphanet Journal of Rare Diseases, 2021)
Background: Hypohidrotic ectodermal dysplasia (HED) is a group of genodermatoses in which deficient ectodysplasin A signalling leads to maldevelopment of skin appendages, various eccrine glands, and teeth. Individuals with HED often have disrupted epithelial barriers and, therefore, were suspected to be more susceptible to coronavirus infection. Methods: 56 households with at least one member who had coronavirus disease of 2019 (COVID-19) were enrolled in a longitudinal study to compare the course of illness, immune responses, and long-term consequences of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) infection in HED patients (n = 15, age 9–52 years) and control subjects of the same age group (n = 149). Results: In 14 HED patients, mild or moderate typical COVID-19 symptoms were observed that lasted for 4–45 days. Fever during the first days sometimes required external cooling measures. The course of COVID-19 was similar to that in control subjects if patients developed antibodies blocking the SARS-CoV-2 spike protein. Five out of six HED patients with completely abrogated ectodysplasin A signalling (83%) suffered from chronic, in two cases very severe fatigue following COVID-19, while only 25% of HED patients with residual activity of this pathway and 21% of control subjects recovering from COVID-19 experienced postinfectious fatigue. Hair loss after COVID-19 was also more frequent among HED patients (64%) than in the control group (13%). Conclusions: HED appears to be associated with an increased risk of long-term consequences of a SARS-CoV-2 infection. Preventive vaccination against COVID-19 should be recommended for individuals affected by this rare genetic disorder.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Chronic fatigue; COVID-19; Hair loss; Hypohidrotic ectodermal dysplasia; SARS-CoV-2

Inhibition of activator protein 1 signaling abrogates transforming growth factor β-mediated activation of fibroblasts and prevents experimental fibrosis - Avouac, Jerome; Palumbo, Katrin; Tomcik, Michal; Zerr, Pawel; Dees, Clara; Horn, Angelika; Maurer, Britta; Akhmetshina, Alfiya; Beyer, Christian; Sadowski, Anika; Schneider, Holm; Shiozawa, Shunichi; et al. (Arthritis and Rheumatism, 2012)
Objective To investigate whether c-Jun and c-Fos contribute to the pathologic activation of fibroblasts in systemic sclerosis (SSc) and to evaluate the antifibrotic potential of selective activator protein 1 (AP-1) inhibition. Methods Expression of c-Jun and c-Fos was determined by real-time polymerase chain reaction (PCR) and immunohistochemical analysis. Fibroblasts were stimulated with transforming growth factor β (TGFβ) and incubated with T-5224, a small-molecule inhibitor of AP-1, or were transfected with small interfering RNA (siRNA) duplexes against c-Jun and c-Fos. Collagen synthesis was quantified by real-time PCR and hydroxyproline assay. Differentiation of resting fibroblasts into myofibroblasts was assessed by staining for α-smooth muscle actin and stress fibers. The antifibrotic potential of T-5224 was evaluated in mouse models of dermal fibrosis induced by bleomycin or by adenoviral overexpression of a constitutively active TGFβ receptor type I. Results Up-regulation of c-Jun and c-Fos was detected in mouse models of SSc and in the skin and dermal fibroblasts of patients with SSc. Stimulation of healthy fibroblasts with TGFβ induced the expression of c-Jun and c-Fos. Treatment with T-5224 or nucleofection with siRNA directed against c-Jun and c-Fos abrogated the profibrotic effects of TGFβ. T-5224 decreased the release of collagen selectively in SSc fibroblasts. T-5224 was well tolerated and prevented dermal fibrosis induced by bleomycin or by adenoviral activation of TGFβ signaling. Conclusion AP-1 is up-regulated in a TGFβ-dependent manner in SSc. The selective AP-1 inhibitor T-5224 reduced collagen synthesis selectively in SSc fibroblasts and efficiently prevented the development of experimental dermal fibrosis. Thus, AP-1 might be a promising new molecular target for the treatment of SSc. Copyright © 2012 by the American College of Rheumatology.
CRIS-Team Scopus Importer:2020-07-01

Inhibition of sumoylation prevents experimental fibrosis - Khodzhigorova, Aisa; Distler, Alfiya; Lang, Veronika; Dees, Clara; Schneider, Holm; Beyer, Christian; Gelse, Kolja; Distler, Oliver; Schett, Georg; Distler, Jörg (Annals of the Rheumatic Diseases, 2012)
Objectives: Fibrosis is a predominant cause of death in systemic sclerosis (SSc). First epigenetic modifications have recently been shown to contribute to activation of SSc fibroblasts. Here, we investigated inhibition of sumoylation as a novel antifibrotic approach. Methods: Sumoylation was inhibited by siRNA-mediated knockdown of the Small Ubiquitin-like MOdifiers (SUMO) E2-conjugating enzyme Ubc9, which is essential for sumoylation. The effects of knockdown of Ubc9 were analysed in bleomycin-induced dermal fibrosis, and in the model of fibrosis induced by overexpression of a constitutively active TGF-beta receptor type I (TBR). SUMO-1 and phosphorylated Smad3 were detected by immunohistochemistry. Results: Increased staining for SUMO-1 was detected in patients with SSc and in experimental fibrosis. Inhibition of sumoylation exerted potent antifibrotic effects and prevented dermal thickening, myofibroblast differentiation and accumulation of collagen induced by bleomycin, or by overexpression of constitutively active TBR. Moreover, knockdown of Ubc9 reduced the accumulation of phosphorylated Smad3 in experimental fibrosis indicating that inhibition of sumoylation may normalise canonical TGF-β signalling in vivo. Conclusions: We demonstrate that inhibition of sumoylation reduces canonical TGF-β signalling and prevents experimental fibrosis in different preclinical models. These data provide first evidence that targeting of aberrant sumoylation may be a novel therapeutic approach for fibrotic diseases.
CRIS-Team Scopus Importer:2020-07-01

Inhibition of tgf-β signaling and decreased apoptosis in iugr-associated lung disease in rats - Alcazar, Miguel Angel Alejandre; Morty, Rory E.; Lendzian, Lisa; Vohlen, Christina; Oestreicher, Iris; Plank, Christian Georg; Schneider, Holm; Doetsch, Joerg (PLoS ONE, 2011)
Intrauterine growth restriction is associated with impaired lung function in adulthood. It is unknown whether such impairment of lung function is linked to the transforming growth factor (TGF)-β system in the lung. Therefore, we investigated the effects of IUGR on lung function, expression of extracellular matrix (ECM) components and TGF-β signaling in rats. IUGR was induced in rats by isocaloric protein restriction during gestation. Lung function was assessed with direct plethysmography at postnatal day (P) 70. Pulmonary activity of the TGF-β system was determined at P1 and P70. TGF-β signaling was blocked in vitro using adenovirus-delivered Smad7. At P70, respiratory airway compliance was significantly impaired after IUGR. These changes were accompanied by decreased expression of TGF-β1 at P1 and P70 and a consistently dampened phosphorylation of Smad2 and Smad3. Furthermore, the mRNA expression levels of inhibitors of TGF-β signaling (Smad7 and Smurf2) were reduced, and the expression of TGF-β-regulated ECM components (e.g. collagen I) was decreased in the lungs of IUGR animals at P1; whereas elastin and tenascin N expression was significantly upregulated. In vitro inhibition of TGF-β signaling in NIH/3T3, MLE 12 and endothelial cells by adenovirus-delivered Smad7 demonstrated a direct effect on the expression of ECM components. Taken together, these data demonstrate a significant impact of IUGR on lung development and function and suggest that attenuated TGF-β signaling may contribute to the pathological processes of IUGR-associated lung disease. © 2011 Alejandre Alcázar et al.
CRIS-Team Scopus Importer:2020-07-01

In vivo evaluation of gene transfer into mesenchymal cells (in view of cartilage repair). - Gelse, Kolja; Schneider, Holm (Methods in Molecular Biology, 2011)
Gene transfer of specific growth factors is suitable for inducing chondrogenic differentiation of -mesenchymal cells to be used for cartilage regeneration. However, extent and quality of repair tissue formation also depend on biomechanical and metabolic influences that can only be studied in vivo. We describe three methods to evaluate viral gene transfer into mesenchymal cells in animal models of articular cartilage defects, e.g., mouse, rat and miniature pig models, focussing on the repair of hyaline cartilage tissue.
CRIS-Team Scopus Importer:2020-07-01

Maternal SARS-CoV-2 infection during pregnancy: possible impact on the infant - Morhart, Patrick; Mardin, Christian; Rauh, Manfred; Juengert, Joerg; Hammersen, Johanna; Kehl, Sven; Schuh, Wolfgang; Maier-Wohlfart, Sigrun; Hermes, Katharina; Neubert, Antje; Schneider, Michael; Hein, Alexander; et al. (European Journal of Pediatrics, 2021)
The risk and potential consequences of mother-to-child transmission of severe acute respiratory syndrome-coronavirus type 2 (SARS-CoV-2) during pregnancy are still a matter of debate. We studied the impact of SARS-CoV-2 infection on 56 complete households, including 27 newborns whose mothers were pregnant when exposed to the virus. Two PCR-confirmed perinatal SARS-CoV-2 transmissions with mild symptoms in affected neonates were recorded. In addition, we observed a severe eye malformation (unilateral microphthalmia, optic nerve hypoplasia, and congenital retinopathy) associated with maternal SARS-CoV-2 infection in weeks 5 and 6 of embryonic development. This embryopathy could not be explained by other infectious agents, genetic factors, drug use, or maternal disease during pregnancy. Eight other women with a history of SARS-CoV-2 infection prior to gestational week 12, however, delivered healthy infants. Conclusion: The repeated occurrence of mother-to-child transmission in our cohort with risks that remain incompletely understood, such as long-term effects and the possibility of an embryopathy, should sensitize researchers and stimulate further studies as well as support COVID-19 vaccination recommendations for pregnant women. Trial registration number: NCT04741412. Date of registration: November 18, 2020What is Known:•Materno-fetal transmission of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) during pregnancy has rarely been reported so far, but was demonstrated in isolated cases.What is New:•In a study of complete households with documented SARS-CoV-2 infection, including a cohort of pregnant women, we observed perinatal coronavirus transmission at a higher frequency than expected.•We also describe a newborn boy with an eye malformation reminiscent of rubella embryopathy but associated with early gestation SARS-CoV-2 infection of his mother.•A coronavirus-related embryopathy, reported here for the first time, is a finding that requires further investigation.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Case report; Coronavirus; Embryopathy; Malformation; Materno-fetal transmission

Mechanical properties of hyaline and repair cartilage studied by nanoindentation - Franke, Oliver; Durst, Karsten; Maier, Verena; Göken, Mathias; Birkholz, Torsten; Schneider, Holm; Hennig, Friedrich; Gelse, Kolja (Acta Biomaterialia, 2007)
Articular cartilage is a highly organized tissue that is well adapted to the functional demands in joints but difficult to replicate via tissue engineering or regeneration. Its viscoelastic properties allow cartilage to adapt to both slow and rapid mechanical loading. Several cartilage repair strategies that aim to restore tissue and protect it from further degeneration have been introduced. The key to their success is the quality of the newly formed tissue. In this study, periosteal cells loaded on a scaffold were used to repair large partial-thickness cartilage defects in the knee joint of miniature pigs. The repair cartilage was analyzed 26 weeks after surgery and compared both morphologically and mechanically with healthy hyaline cartilage. Contact stiffness, reduced modulus and hardness as key mechanical properties were examined in vitro by nanoindentation in phosphate-buffered saline at room temperature. In addition, the influence of tissue fixation with paraformaldehyde on the biomechanical properties was investigated. Although the repair process resulted in the formation of a stable fibrocartilaginous tissue, its contact stiffness was lower than that of hyaline cartilage by a factor of 10. Fixation with paraformaldehyde significantly increased the stiffness of cartilaginous tissue by one order of magnitude, and therefore, should not be used when studying biomechanical properties of cartilage. Our study suggests a sensitive method for measuring the contact stiffness of articular cartilage and demonstrates the importance of mechanical analysis for proper evaluation of the success of cartilage repair strategies.
Created from Fastlane, Scopus look-up
Keywords: Cartilage; Nanoindentation; Soft tissues; Stiffness; Storage effect

Methods for the Administration of EDAR Pathway Modulators in Mice - Schuepbach-Mallepell, Sonia; Kowalczyk-Quintas, Christine; Dick, Angela; Eslami, Mahya; Vigolo, Michele; Headon, Denis J.; Cheeseman, Michael; Schneider, Holm; Schneider, Pascal (The TNF Superfamily, 2021)
Genetic deficiency of ectodysplasin A (EDA) causes X-linked hypohidrotic ectodermal dysplasia, a congenital condition characterized by the absence or abnormal formation of sweat glands, teeth, and several skin appendages. Stimulation of the EDA receptor (EDAR) with agonists in the form of recombinant EDA or anti-EDAR antibodies can compensate for the absence of Eda in a mouse model of Eda deficiency, provided that agonists are administered in a timely manner during fetal development. Here we provide detailed protocols for the administration of EDAR agonists or antagonists, or other proteins, by the intravenous, intraperitoneal, and intra-amniotic routes as well as protocols to collect blood, to visualize sweat gland function, and to prepare skulls in mice.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Amniotic fluid; Ectodermal dysplasia; EDAR signaling; Protein replacement therapy; Route of administration

Molecular Pathway-Based Classification of Ectodermal Dysplasias: First Five-Yearly Update - Peschel, Nicolai; Wright, John T.; Koster, Maranke I.; Clarke, Angus J.; Tadini, Gianluca; Fete, Mary; Hadj-Rabia, Smail; Sybert, Virginia P.; Norderyd, Johanna; Maier-Wohlfart, Sigrun; Fete, Timothy J.; Pagnan, Nina; et al. (Genes, 2022)
To keep pace with the rapid advancements in molecular genetics and rare diseases research, we have updated the list of ectodermal dysplasias based on the latest classification approach that was adopted in 2017 by an international panel of experts. For this purpose, we searched the databases PubMed and OMIM for the term "ectodermal dysplasia", referring mainly to changes in the last 5 years. We also tried to obtain information about those diseases on which the last scientific report appeared more than 15 years ago by contacting the authors of the most recent publication. A group of experts, composed of researchers who attended the 8th International Conference on Ectodermal Dysplasias and additional members of the previous classification panel, reviewed the proposed amendments and agreed on a final table listing all 49 currently known ectodermal dysplasias for which the molecular genetic basis has been clarified, including 15 new entities. A newly reported ectodermal dysplasia, linked to the gene LRP6, is described here in more detail. These ectodermal dysplasias, in the strict sense, should be distinguished from syndromes with features of ectodermal dysplasia that are related to genes extraneous to the currently known pathways involved in ectodermal development. The latter group consists of 34 syndromes which had been placed on the previous list of ectodermal dysplasias, but most if not all of them could actually be classified elsewhere. This update should streamline the classification of ectodermal dysplasias, provide guidance to the correct diagnosis of rare disease entities, and facilitate the identification of individuals who could benefit from novel treatment options.
CRIS-Team WoS Importer:2023-01-06

Molecular Therapies - Schneider, Holm; Schneider, Pascal (Springer Nature, 2025)
This chapter describes the development of molecular therapies for X-linked hypohidrotic ectodermal dysplasia (XLHED), the most common ectodermal dysplasia syndrome, and for the cutaneous and ocular manifestations of p63-associated syndromes. Large parts of the text are based on the following previously published journal article by Holm Schneider: “Ectodermal dysplasias: New perspectives on the treatment of so far immedicable genetic disorders”, Front Genet. 13:1000744, doi: 10.3389/fgene.2022.1000744; available under the terms of the Creative Commons Attribution License (CC BY).
CRIS-Team Scopus Importer:2025-05-02
Keywords: Ectodysplasin A; Molecular therapy; Neonatal Fc receptor; P63 PRIMA-1MET

Multidisciplinary Approach to Ectodermal Dysplasia - Tadini, Gianluca; Wright, John Timothy; Hadj-Rabia, Smail; Schneider, Holm (Springer Nature, 2025)

Mutational spectrum in 101 patients with hypohidrotic ectodermal dysplasia and breakpoint mapping in independent cases of rare genomic rearrangements - Wohlfart, Sigrun; Hammersen, Johanna; Schneider, Holm (Journal of Human Genetics, 2016)
Hypohidrotic ectodermal dysplasia (HED), a rare and heterogeneous hereditary disorder, is characterized by deficient development of multiple ectodermal structures including hair, sweat glands and teeth. If caused by mutations in the genes EDA, EDA1R or EDARADD, phenotypes are often very similar as the result of a common signaling pathway. Single-nucleotide polymorphisms (SNPs) affecting any gene product in this pathway may cause inter- and intrafamilial variability. In a cohort of 124 HED patients, genotyping was attempted by Sanger sequencing of EDA, EDA1R, EDARADD, TRAF6 and EDA2R and by multiplex ligation-dependent probe amplification (MLPA). Pathogenic mutations were detected in 101 subjects with HED, affecting EDA, EDA1R and EDARADD in 88%, 9% and 3% of the cases, respectively, and including 23 novel mutations. MLPA revealed exon copy-number variations in five unrelated HED families (two deletions and three duplications). In four of them, the genomic breakpoints could be localized. The EDA1R variant rs3827760 (p.Val370Ala), known to lessen HED-related symptoms, was found only in a single individual of Asian origin, but in none of the 123 European patients. Another SNP, rs1385699 (p.Arg57Lys) in EDA2R, however, appeared to have some impact on the hair phenotype of European subjects with EDA mutations.
EVALuna2:33878

Natural history and clinical outcome of junctional epidermolysis bullosa generalized intermediate due to a LAMA3 mutation - Reimer, A.; Schwieger-Briel, A.; He, Y.; Leppert, J.; Schauer, F.; Kiritsi, D.; Schneider, Holm; Ott, H.; Bruckner-Tuderman, L.; Has, C. (British Journal of Dermatology, 2018)
EVALuna2:35487

Natural history of X-linked hypohidrotic ectodermal dysplasia: a 5-year follow-up study - Wohlfart, Sigrun; Meiller, Ralph; Hammersen, Johanna; Park, Jung; Menzel-Severing, Johannes; Melichar, Volker O.; Huttner, Kenneth; Johnson, Ramsey; Porte, Florence; Schneider, Holm (Orphanet Journal of Rare Diseases, 2020)
BACKGROUND: X-linked hypohidrotic ectodermal dysplasia (XLHED) is caused by pathogenic variants of the gene EDA disrupting the prenatal development of ectodermal derivatives. Cardinal symptoms are hypotrichosis, lack of teeth, and hypo- or anhidrosis, but the disease may also evoke other clinical problems. This study aimed at investigating the clinical course of XLHED in early childhood as the basis for an evaluation of the efficacy of potential treatments. METHODS: 25 children (19 boys and 6 girls between 11 and 35 months of age) with genetically confirmed XLHED were enrolled in a long-term natural history study. Clinical data were collected both retrospectively using parent questionnaires and medical records (pregnancy, birth, infancy) and prospectively until the age of 60 months. General development, dentition, sweating ability, ocular, respiratory, and skin involvement were assessed by standardized clinical examination and yearly quantitative surveys. RESULTS: All male subjects suffered from persistent anhidrosis and heat intolerance, although a few sweat ducts were detected in some patients. Sweating ability of girls with XLHED ranged from strongly reduced to almost normal. In the male subjects, 1-12 deciduous teeth erupted and 0-8 tooth germs of the permanent dentition became detectable. Tooth numbers were higher but variable in the female group. Most affected boys had no more than three if any Meibomian glands per eyelid, most girls had fewer than 10. Many male subjects developed additional, sometimes severe health issues, such as obstructive airway conditions, chronic eczema, or dry eye disease. Adverse events included various XLHED-related infections, unexplained fever, allergic reactions, and retardation of psychomotor development. CONCLUSIONS: This first comprehensive study of the course of XLHED confirmed the early involvement of multiple organs, pointing to the need of early therapeutic intervention.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Dry eye; Ectodysplasin A; Heat intolerance; Hypohidrotic ectodermal dysplasia; Natural history; Oligodontia

No evidence for preferential X-chromosome inactivation as the main cause of divergent phenotypes in sisters with X-linked hypohidrotic ectodermal dysplasia - Körber, Laura; Schneider, Holm; Fleischer, Nicole; Maier-Wohlfart, Sigrun (Orphanet Journal of Rare Diseases, 2021)
Background: X-linked hypohidrotic ectodermal dysplasia (XLHED), a rare genetic disorder, affects the normal development of ectodermal derivatives, such as hair, skin, teeth, and sweat glands. It is caused by pathogenic variants of the gene EDA and defined by a triad of hypotrichosis, hypo- or anodontia, and hypo- or anhidrosis which may lead to life-threatening hyperthermia. Although female carriers are less severely affected than male patients, they display symptoms, too, with high phenotypic variability. This study aimed to elucidate whether phenotypic differences in female XLHED patients with identical EDA genotypes might be explained by deviating X-chromosome inactivation (XI) patterns. Methods: Six families, each consisting of two sisters with the same EDA variant and their parents (with either mother or father being carrier of the variant), participated in this study. XLHED-related data like sweating ability, dental status, facial dysmorphism, and skin issues were assessed. We determined the women`s individual XI patterns in peripheral blood leukocytes by the human androgen receptor assay and collated the results with phenotypic features. Results: The surprisingly large inter- and intrafamilial variability of symptoms in affected females was not explicable by the pathogenic variants. Our cohort showed no higher rate of nonrandom XI in peripheral blood leukocytes than the general female population. Furthermore, skewed XI patterns in favour of the mutated alleles were not associated with more severe phenotypes. Conclusions: We found no evidence for preferential XI in female XLHED patients and no distinct correlation between XLHED-related phenotypic features and XI patterns. Phenotypic variability seems to be evoked by other genetic or epigenetic factors.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Ectodysplasin A; Female carriers; Genotype–phenotype correlation; X-chromosome inactivation; X-linked hypohidrotic ectodermal dysplasia

No juvenile arterial hypertension in sheep multiples despite reduced nephron numbers - Muehle, Anja; Mühle, Christiane; Amann, Kerstin Ute; Dötsch, Jörg; Nuesken, Kai-Dietrich; Boltze, Johannes; Schneider, Holm (Pediatric Nephrology, 2010)
Low birth weight is associated with an increased risk of metabolic dysfunction and arterial hypertension in later life. Because of their reduced birth weight twins have been used repeatedly as a natural model to investigate prenatal programming of hypertension. To reveal an early impact of lower nephron endowment on blood pressure, we performed a longitudinal study on lambs from single, twin and triplet pregnancies. The lambs were studied from birth until adulthood, including regular blood analyses, measurements of body weight and blood pressure and post-mortem estimation of glomerular numbers. Relative weight differences between multiples and singletons at birth were -28% for twins and -44% for triplets, respectively. Some lambs showed rapid catch-up growth. Total nephron number of twins and triplets was reduced by 21 and 37% with respect to that of singletons (p∈<∈0.01). However, multiples did not show increased blood pressure within the time frame of this study. No gender-specific effect was observed. Plasma concentrations of creatinine, urea, electrolytes or osmolality also did not differ. Our data indicate that the previously reported postnatal blood pressure differences between sheep multiples and singletons are a time-limited phenomenon. During infancy and adolescence, a reduced nephron number in sheep multiples is neither associated with increased blood pressure nor reflected by plasma parameters. © 2010 IPNA.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Blood pressure; Nephron number; Prenatal programming

Noninvasive Prenatal Diagnosis of Hypohidrotic Ectodermal Dysplasia by Tooth Germ Sonography - Wuensche, S.; Juengert, J.; Faschingbauer, Florian; Mommsen, H.; Goecke, T.; Schwanitz, K.; Stepan, H.; Schneider, Holm (Ultraschall in der Medizin, 2015)
Hypohidrotic ectodermal dysplasia, a potentially life-threatening heritable disorder, may be recognized already in utero by characteristic features such as oligodontia and mandibular hypoplasia. As therapeutic options and prognosis depend on the time point of diagnosis, early recognition was attempted during routine prenatal ultrasound examinations.Fetuses of nine pregnant women (one triplet and eight singleton pregnancies) with family histories of hypohidrotic ectodermal dysplasia were investigated by sonography between the 20th and 24th week of gestation.In 4 male and 2 female fetuses reduced amounts of tooth germs were detected, whereas 5 fetal subjects showed the normal amount. Three-dimensional ultrasound evaluation revealed mandibular hypoplasia in 5 of the 6 fetuses with oligodontia. Molecular genetic analysis and/or clinical findings after birth confirmed the prenatal sonographic diagnosis in each subject.In subjects with a family history of hypohidrotic ectodermal dysplasia, the diagnosis of this rare condition can be established noninvasively by sonography in the second trimester of pregnancy. Early recognition of the disorder may help to prevent dangerous hyperthermic episodes in infancy and may allow timely therapeutic intervention
EVALuna2:17430

Parecoxib does not suppress thromboxane synthesis in newborn piglets with group B streptococcal sepsis - Nögel, Stephanie; Chada, Martin; Schmidt, Ariana; Bosselmann, Stephan; Kandler, Michael; Schweer, Horst; Watzer, Bernhard; Schneider, Holm; Gessner, André; Rascher, Wolfgang (Prostaglandins & Other Lipid Mediators, 2009)
Group B streptococci (GBS) cause fatal sepsis in newborns. Strong activation of thromboxane synthesis is assumed to correlate with severe pulmonary hypertension. In this study we compared the impact of indomethacin versus parecoxib on hemodynamics and outcome and investigated the pharmacological effects on thromboxane synthesis and EP-3 receptor gene expression. Whereas both parecoxib and indometacin reduced expression of thromboxane synthase and EP-3 receptor in infected lung tissue, parecoxib did not suppress urine levels of thromboxane like indometacin. We presume that COX-2 inhibition in GBS sepsis is associated with enhanced thrombogenicity. © 2009 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Group b streptococcal sepsis; Parecoxib; Thromboxane

Prenatal Correction of X-Linked Hypohidrotic Ectodermal Dysplasia - Schneider, Holm; Faschingbauer, Florian; Schuepbach-Mallepell, Sonia; Koerber, Iris; Wohlfart, Sigrun; Dick, Angela; Wahlbuhl, Mandy; Kowalczyk-Quintas, Christine; Vigolo, Michele; Kirby, Neil; Tannert, Corinna; Rompel, Oliver; et al. (New England Journal of Medicine, 2018)
Genetic deficiency of ectodysplasin A (EDA) causes X-linked hypohidrotic ectodermal dysplasia (XLHED), in which the development of sweat glands is irreversibly impaired, an condition that can lead to life-threatening hyperthermia. We observed normal development of mouse fetuses with Eda mutations after they had been exposed in utero to a recombinant protein that includes the receptor-binding domain of EDA. We administered this protein intraamniotically to two affected human twins at gestational weeks 26 and 31 and to a single affected human fetus at gestational week 26; the infants, born in week 33 (twins) and week 39 (singleton), were able to sweat normally, and XLHED-related illness had not developed by 14 to 22 months of age. (Funded by Edimer Pharmaceuticals and others.).
EVALuna2:35486

Prenatal therapy in developmental disorders: drug targeting via intra-amniotic injection to treat X-linked hypohidrotic ectodermal dysplasia - Hermes, Katharina; Schneider, Pascal; Krieg, Peter; Anh Thu Dang; Huttner, Kenneth; Schneider, Holm (Journal of Investigative Dermatology, 2014)
EVALuna2:18898

Prenatal treatment of X-linked hypohidrotic ectodermal dysplasia using recombinant ectodysplasin in a canine model - Margolis, Carol A.; Schneider, Pascal; Huttner, Kenneth; Kirby, Neil; Houser, Timothy P.; Wildman, Lee; Grove, Gary L.; Schneider, Holm; Casal, Margret L. (Journal of Pharmacology and Experimental Therapeutics, 2019)
X-linked hypohidrotic ectodermal dysplasia (XLHED) is caused by defects in the EDA gene that inactivate the function of ectodysplasin A1 (EDA1). This leads to abnormal development of eccrine glands, hair follicles, and teeth, and to frequent respiratory infections. Previous studies in the naturally occurring dog model demonstrated partial prevention of the XLHED phenotype by postnatal administration of recombinant EDA1. The results suggested that a single or two temporally spaced injections of EDI200 prenatally might improve the clinical outcome in the dog model. Fetuses received ultrasound-guided EDI200 intra-amniotically at gestational days 32 and 45, or 45 or 55 alone (of a 65-day pregnancy). Growth rates, lacrimation, hair growth, meibomian glands, sweating, dentition, and mucociliary clearance were compared in treated and untreated XLHED-affected dogs, and in heterozygous and wild-type control dogs. Improved phenotypic outcomes were noted in the earlier and more frequently treated animals. All animals treated prenatally showed positive responses compared with untreated dogs with XLHED, most notably in the transfer of moisture through paw pads, suggesting improved onset of sweating ability and restored meibomian gland development. These results exemplify the feasibility of ultrasound-guided intra-amniotic injections for the treatment of developmental disorders, with improved formation of specific EDA1-dependent structures in dogs with XLHED.
CRIS-Team Scopus Importer:2019-09-17

Prevalence and prevention of severe complications of hypohidrotic ectodermal dysplasia in infancy - Blueschke, Gert; Nuesken, Kai-Dietrich; Schneider, Holm (Early Human Development, 2010)
Objective: To re-evaluate the mortality of hypohidrotic ectodermal dysplasia (HED) and the prevalence of hyperpyrexia and possible neurological sequelae in affected infants. Study design: A cross-sectional postal survey was conducted among parents of 100 children with ectodermal dysplasia who had been registered with the German-Swiss-Austrian patient support group at any time point within the past 10. years. Detailed questionnaires referring to the first year of life were evaluated statistically. Results: 63% of parents returned completed surveys, identifying 57% of children as patients with X-linked HED and 20% as patients with autosomal HED or HED of unknown origin. Of those two groups, 17 infants had been placed in an incubator after birth, where body temperature recording proved to be of utmost importance. In 94% of all HED patients, episodes of unexplained fever were observed during the first year of life. X-linked HED was associated with frequent airway infections. Febrile seizures occurred in 5.9% of infants with X-linked HED and in 17% of the other HED patients. Developmental retardation was reported for 15% and 25%, respectively. Prognosis depended on the type of genetic defect and the time point of diagnosis. Except for one all patients survived infancy. Early recognition of the disease was aided by vigilant neonatal care and consulting a dermatologist or geneticist. Adequate instruction of the parents and networking with patient support groups also reduced the risks associated with HED. Conclusions: Today, mortality of HED and the risk of hyperthermic brain damage are still increased, but lower than reported previously. © 2010 Elsevier Ltd.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Ectodermal dysplasia; Febrile seizure; Hyperthermia; Sudden infant death

Prevalence of SARS-CoV-2 in Pregnant Women Assessed by RT-PCR in Franconia, Germany: First Results of the SCENARIO Study (SARS-CoV-2 prEvalence in pregNAncy and at biRth In FrancOnia) - Hein, Alexander; Kehl, Sven; Häberle, Lothar; Tiemann, Carsten; Peuker, Rebecca; Mereutanu, Denise; Stumpfe, Florian; Faschingbauer, Florian; Meyer-Schlinkmann, Kirstin; Koch, Martin C.; Kainer, Franz; Dammer, Ulf; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Purpose Detection of SARS-CoV-2-infected pregnant women admitted to maternity units during a pandemic is crucial. In addition to the fact that pregnancy is a risk factor for severe COVID-19 and that medical surveillance has to be adjusted in infected women and their offspring, knowledge about infection status can provide the opportunity to protect other patients and healthcare workers against virus transmission. The aim of this prospective observational study was to determine the prevalence of SARS-CoV-2 infection among pregnant women in the hospital setting. Material and Methods All eligible pregnant women admitted to the nine participating hospitals in Franconia, Germany, from 2 June 2020 to 24 January 2021 were included. COVID-19-related symptoms, secondary diseases and pregnancy abnormalities were documented. SARS-CoV-2 RNA was detected by RT-PCR from nasopharyngeal swabs. The prevalence of acute SARS-CoV-2 infection was estimated by correcting the positive rate using the Rogan-Gladen method. The risk of infection for healthcare workers during delivery was estimated using a risk calculator. Results Of 2414 recruited pregnant women, six were newly diagnosed RT-PCR positive for SARS-CoV-2, which yielded a prevalence of SARS-CoV-2 infection of 0.26% (95% CI, 0.10-0.57%). Combining active room ventilation and wearing FFP2 masks showed an estimated reduction of risk of infection for healthcare workers in the delivery room to < 1%. Conclusions The prevalence of newly diagnosed SARS-CoV-2 infection during pregnancy in this study is low. Nevertheless, a systematic screening in maternity units during pandemic situations is important to adjust hygienic and medical management. An adequate hygienic setting can minimise the calculated infection risk for medical healthcare workers during patients' labour.
CRIS-Team Scopus Importer:2022-02-25
Keywords: COVID-19; infection; pregnancy; prevalence; SARS-CoV-2

Protocol for the Phase 2 EDELIFE Trial Investigating the Efficacy and Safety of Intra-Amniotic ER004 Administration to Male Subjects with X-Linked Hypohidrotic Ectodermal Dysplasia - Schneider, Holm; Hadj-Rabia, Smail; Faschingbauer, Florian; Bodemer, Christine; Grange, Dorothy K.; Norton, Mary E.; Cavalli, Riccardo; Tadini, Gianluca; Stepan, Holger; Clarke, Angus; Guillén-Navarro, Encarna; Maier-Wohlfart, Sigrun; et al. (Genes, 2023)
X-linked hypohidrotic ectodermal dysplasia (XLHED) is a rare genetic disorder characte-rised by abnormal development of the skin and its appendages, such as hair and sweat glands, the teeth, and mucous glands of the airways, resulting in serious, sometimes life-threatening complications like hyperthermia or recurrent respiratory infections. It is caused by pathogenic variants of the ectodysplasin A gene (EDA). Most affected males are hemizygous for EDA null mutations that lead to the absence or inactivity of the signalling protein ectodysplasin A1 (EDA1) and, thus, to the full-blown phenotype with inability to perspire and few if any teeth. There are currently no long-term treatment options for XLHED. ER004 represents a first-in-class protein replacement molecule designed for specific, high-affinity binding to the endogenous EDA1 receptor (EDAR). Its proposed mechanism of action is the replacement of missing EDA1 in yet unborn patients with XLHED. Once bound to EDAR, ER004 activates the EDA/NFκB signalling pathway, which triggers the transcription of genes involved in the normal development of multiple tissues. Following preclinical studies, named-patient use cases demonstrated significant potential of ER004 in affected males treated in utero during the late second and third trimesters of pregnancy. In order to confirm these results, we started the EDELIFE trial, a prospective, open-label, genotype-match controlled, multicentre clinical study to investigate the efficacy and safety of intra-amniotic ER004 administration as a prenatal treatment for male subjects with XLHED. This article summarises the rationale, the study protocol, ethical issues of the trial, and potential pitfalls.
CRIS-Team Scopus Importer:2023-02-24
Keywords: anhidrosis; clinical trial; ectodermal dysplasia; ectodysplasin A; fetal therapy; protein replacement; sweat glands

Reduced Perinatal Leptin Availability May Contribute to Adverse Metabolic Programming in a Rat Model of Uteroplacental Insufficiency - Nuesken, Eva; Wohlfarth, Maria; Lippach, Gregor; Rauh, Manfred; Schneider, Holm; Doetsch, Joerg; Nuesken, Kai-Dietrich (Endocrinology, 2016)
Leptin availability in perinatal life critically affects metabolic programming. We tested the hypothesis that uteroplacental insufficiency and intrauterine stress affect perinatal leptin availability in rat offspring. Pregnant rats underwent bilateral uterine vessel ligation (LIG; n = 14), sham operation (SOP; n = 12), or no operation (controls, n = 14). Fetal livers (n = 180), placentas (n = 180), and maternal blood were obtained 4 hours (gestational day [E] 19), 24 hours (E20), and 72 hours (E22) after surgery. In the offspring, we took blood samples on E22 (n = 44), postnatal day (P) 1 (n = 29), P2 (n = 16), P7 (n = 30), and P12 (n = 30). Circulating leptin (ELISA) was significantly reduced in LIG (E22, P1, P2) and SOP offspring (E22). Postnatal leptin surge was delayed in LIG but was accelerated in SOP offspring. Placental leptin gene expression (quantitative RT-PCR) was reduced in LIG (E19, E20, E22) and SOP (E20, E22). Hepatic leptin receptor (Lepr-a, mediating leptin degradation) gene expression was increased in LIG fetuses (E20, E22) only. Surprisingly, hypoxia-inducible factors (Hif; Western blot) were unaltered in placentas and were reduced in the livers of LIG (Hif1a, E20; Hif2a, E19, E22) and SOP (Hif2a, E19) fetuses. Gene expression of prolyl hydroxylase 3, a factor expressed under hypoxic conditions contributing to Hif degradation, was increased in livers of LIG (E19, E20, E22) and SOP (E19) fetuses and in placentas of LIG and SOP (E19). In summary, reduced placental leptin production, increased fetal leptin degradation, and persistent perinatal hypoleptinemia are present in intrauterine growth restriction offspring, especially after uteroplacental insufficiency, and may contribute to perinatal programming of leptin resistance and adiposity in later life.
EVALuna2:33880

Reliability of prenatal detection of X-linked hypohidrotic ectodermal dysplasia by tooth germ sonography - Hammersen, Johanna; Wohlfart, Sigrun; Goecke, Tamme W.; Köninger, Angela; Stepan, Holger; Gallinat, Ralph; Morris, Susan; Bücher, Katharina; Clarke, Angus; Wünsche, Stephanie; Beckmann, Matthias; Schneider, Holm; et al. (Prenatal Diagnosis, 2019)
Objective: In X-linked hypohidrotic ectodermal dysplasia (XLHED), dysfunction of ectodysplasin A1 (EDA1) due to EDA mutations results in malformation of hair, teeth, and sweat glands. Hypohidrosis, which can cause life-threatening hyperthermia, is amenable to intrauterine therapy with recombinant EDA1. This study aimed at evaluating tooth germ sonography as a noninvasive means to identify affected fetuses in pregnant carrier women. Methods: Sonography, performed at 10 study sites between gestational weeks 18 and 28, led to the diagnosis of XLHED if fewer than six tooth germs were detected in mandible or maxilla. The assessment was verified postnatally by EDA sequencing and/or clinical findings. Estimated fetal weights and postnatal weight gain of boys with XLHED were assessed using appropriate growth charts. Results: In 19 of 38 sonographic examinations (23 male and 13 female fetuses), XLHED was detected prenatally. The prenatal diagnosis proved to be correct in 37 cases; one affected male fetus was missed. Specificity and positive predictive value were both 100%. Tooth counts obtained by clinical examination corresponded well with findings on panoramic radiographs. We observed no weight deficits of subjects with XLHED in utero but occasionally during infancy. Conclusion: Tooth germ sonography is highly specific and reliable in detecting XLHED prenatally.
CRIS-Team Scopus Importer:2019-08-27

Reproductive decision-making by women with X-linked hypohidrotic ectodermal dysplasia - Leo, B.; Schneider, Holm; Hammersen, J. (Journal of the European Academy of Dermatology and Venereology, 2022)
Background: In X-linked hypohidrotic ectodermal dysplasia (XLHED), ectodysplasin A1 (EDA1) deficiency results in malformation of hair, teeth and sweat glands. Lack of sweating which can cause life-threatening hyperthermia is amenable to intrauterine therapy with recombinant EDA1. Objectives: This study aimed at evaluating reproductive decision-making by women with XLHED and at clarifying the potential impact of a prenatal treatment option. Methods: In a retrospective cross-sectional analysis, a 75-item questionnaire filled in by 50 women with XLHED (age 19–49 years) was assessed. Results: Sixteen women (32%) prevented pregnancies because of the risk to pass on XLHED; 15 considered assisted reproduction for the same reason. Twelve women had a history of miscarriage, stillbirth or abortion, and three women reported on previous abortion of affected fetuses. When imagining to be pregnant, all except one showed interest in prenatal diagnosis of XLHED and in the possibility of treatment before birth. In 13 out of 50 women (26%), XLHED if detected prenatally would have impact on the continuation of pregnancy. Among 35 mothers of at least one affected child, XLHED had rarely been diagnosed during the first pregnancy (17%) but regularly during subsequent pregnancies (77%). Becoming aware of the condition before birth had caused a moral conflict for 50% of these women. Subjects with an affected child less frequently considered assisted reproduction to prevent XLHED (P < 0.05). In 69% of the women who reported an effect of XLHED on family planning, a prenatal treatment option for this disease would influence their decision-making. Conclusions: Many pregnant XLHED carriers who seek prenatal diagnosis experience moral conflicts. A prenatal treatment option would have strong impact on reproductive decisions, underlining the importance of adequate professional counselling.
CRIS-Team Scopus Importer:2022-06-17

Safety and immunogenicity of Fc-EDA, a recombinant ectodysplasin A1 replacement protein, in human subjects - Körber, Iris; Klein, Ophir D.; Morhart, Patrick; Faschingbauer, Florian; Grange, Dorothy K.; Clarke, Angus; Bodemer, Christine; Maitz, Silvia; Huttner, Kenneth; Kirby, Neil; Durand, Caroline; Schneider, Holm (British Journal of Clinical Pharmacology, 2020)
In X-linked hypohidrotic ectodermal dysplasia, the most frequent ectodermal dysplasia, an inherited deficiency of the signalling protein ectodysplasin A1 (EDA1) impairs the development of the skin and its appendages, various eccrine glands, and dentition. The severe hypohidrosis common to X-linked hypohidrotic ectodermal dysplasia patients may lead to life-threatening hyperthermia, especially during hot weather or febrile illness. Fc-EDA, an EDA1 replacement protein known to prevent the disease in newborn animals, was tested in 2 clinical trials (human adults and neonates) and additionally administered under compassionate use to 3 infants in utero. The data support the safety of Fc-EDA and efficacy if applied prenatally. Anti-drug antibodies were detected after intravenous administration in adult males and nonpregnant females, but not in pregnant women when Fc-EDA was delivered intra-amniotically. Most importantly, there was no detectable immune response to the investigational drug in neonates treated by intravenous infusions and in infants who had received Fc-EDA in utero. In conclusion, the safety profile of this drug encourages further development of prenatal EDA1 replacement therapy.
CRIS-Team Scopus Importer:2020-05-02
Keywords: drug safety; ectodermal dysplasia; ectodysplasin A; immunogenicity; prenatal therapy; protein replacement

SARS-CoV-2-Infektion in der Schwangerschaft und Auftreten von angeborenen Fehlbildungen – Besteht ein Zusammenhang? Auswertung von 8032 Schwangerschaften aus dem CRONOS-Register - Hofbauer, Anna; Schneider, Holm; Kehl, Sven; Reutter, Heiko Martin; Pecks, Ulrich; Andresen, Kristin; Morhart, Patrick (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
Background Based on single case reports, the COVID-19 Related Obstetric and Neonatal Outcome Study (CRONOS) registry, sponsored by the German Society for Perinatal Medicine (DGPM), investigated the likelihood that SARS-CoV-2 infections of the mother in (early) pregnancy cause embryopathies and/or fetopathies. Material/Methods The CRONOS registry enrolled a total of 8032 women with confirmed SARS-CoV-2 infection during pregnancy at more than 130 participating hospitals from April 2020 to February 2023. Both maternal and fetal data were documented and the anonymized multicenter data were analyzed. Results Of 7142 fully documented pregnancies (including postnatal data), 140 showed congenital malformations. 8.57% of the mothers had had a SARS-CoV-2-infection in the 1st trimester and 36.43% in the 2nd trimester. In 66 cases with congenital malformations (47.14%), the malformation was only detected after the diagnosis of a maternal SARS-CoV-2 infection. The overall prevalence of congenital malformations in this cohort was 1.96%, compared to a prevalence of 2.39% reported in the EUROCAT (European network of population-based registries for the epidemiological surveillance of congenital anomalies) pre-pandemic registry between 2017-2019. Discussion Our multicenter data argue against a link between maternal SARS-CoV-2 infection in early pregnancy and congenital malformation.
CRIS-Team Scopus Importer:2024-02-23
Keywords: Coronavirus; COVID-19; CRONOS-registry; embryopathy; fetopathy; malformations

Second International Conference on a classification of ectodermal dysplasias: development of a multiaxis model - Salinas, Carlos F.; Irvine, Alan D.; Itin, Peter H.; Di Giovanna, John J.; Schneider, Holm; Clarke, Angus J.; Mcgovern, Laura Sternesky; Fete, Mary (American Journal of Medical Genetics Part A, 2014)
Ectodermal dysplasias (EDs) comprise a large clinically and etiologically heterogeneous group of genetic disorders characterized by abnormalities in tissues derived from the embryonic ectoderm. Controversy exists over which syndromes should be classified as EDs and which should be excluded from the classification. The challenge will be to balance comprehensiveness within the classification with usability and accessibility so that the benefits truly serve the needs of researchers, health-care providers, and ultimately the individuals and families directly affected by EDs. The overarching goal of the Second International Conference was to develop a consensus on EDs classifications, with the ultimate goal of creating a system that integrates clinical and molecular knowledge, using an interactive Internet-based database that clinicians, researchers, and laymen can use. The Conference, brought together a group of experts from around the world, including a diverse health-care providers, researchers, patient advocate representatives, and administrators. The Conference was modeled after the 2008 conference, with plenary sessions, scientific updates, and small group discussions. Based on the present clinical knowledge, new molecular advances and both coupled with new bioinformatics developments, the participants agree to develop a multi-axis system approach for the classification of EDs. The multi-axis approach will include a clinical/phenotype axis, a gene-based axis, and a functional/pathways axis. The significance of the conference outcomes includes, a new classification approach that will foster a better understanding of EDs, open new fields of research and develop a nosologic approach that may have broad implications for classifying other hereditary conditions.
EVALuna2:18896

Stammzellen aus Nabelschnurblut - ein besonderes Gut: Informationen für eine fachärztliche Beratung der Schwangeren - Goecke, Tamme W.; Jud, Sebastian; Weisbach, Volker Günter; Bender, A. W.; Schneider, Holm (Geburtshilfe und Frauenheilkunde, 2010)
CRIS-Team Scopus Importer:2020-07-01

Strong hypoxia reduces leptin synthesis in purified primary human trophoblasts - Nuesken, E.; Herrmann, Y.; Wohlfarth, M.; Goecke, Tamme W.; Appel, S.; Schneider, Holm; Doetsch, J.; Nuesken, K. D. (Placenta, 2015)
Introduction Oxygen availability severely affects placental function. During placental hypoxia, stabilization of hypoxia inducible factors (HIFs) affects transcription, and leptin gene expression concomitantly increases in vivo and in vitro. However, a causal relationship is uncertain.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Hypoxia; Leptin/leptin receptor; Placenta; Trophoblast

Surprising prenatal toxicity of epidermal lipoxygenase-3 - Vierling, F.; Dick, Angela; Wahlbuhl, Mandy; Krieg, P.; Henke, Christine; Ruebner, M.; Schneider, Holm (Placenta, 2014)
Metabolites of the epidermal lipoxygenase-3 (eLOX-3) are involved in various metabolic pathways. Most unexpectedly, intra-amniotic delivery of eLOX-3 to mice at gestational day 14.5, both via an adenoviral vector and as recombinant protein, resulted in fetal growth restriction and intrauterine death. Periodic acid-Schiff staining and RT-PCR analysis of placentae from fetuses exposed to eLOX-3 indicated a lack of glycogen trophoblasts in the junctional zone. Placenta-specific gene expression was altered. Thus, the observed prenatal toxicity of eLOX-3 could be due to a strong effect on placental development.
EVALuna2:17431

Sustained Need for High-Dose Zinc Supplementation in Children With Acrodermatitis Enteropathica - Hammersen, Johanna; Has, Cristina; Galiano, Matthias; Lindner, Martin; Rossi, Rainer; Kohlhase, Juergen; Schneider, Holm (Clinical Pediatrics, 2018)
EVALuna2:34298

Sweating ability and genotype in individuals with X-linked hypohidrotic ectodermal dysplasia - Schneider, Holm; Hammersen, Johanna; Preisler-Adams, Sabine; Huttner, Kenneth; Rascher, Wolfgang; Bohring, Axel (Journal of Medical Genetics, 2011)
Background: X-linked hypohidrotic ectodermal dysplasia (XLHED), the most common type of ectodermal dysplasia, is caused by EDA gene mutations. Reduced sweating contributes substantially to XLHED associated morbidity and mortality. To characterise the genotypeephenotype relationship, sweat gland function was assessed non-invasively in XLHED patients and healthy controls. Subjects and methods: In 36 genotyped XLHED patients and 29 control subjects aged 0e57 years, pilocarpine-induced sweat volume, palmar sweat pore density, and palmar skin conductance before and after stimulation were determined. Results: Among 31 XLHED males, 14 had neither detectable sweat pores nor inducible sweating, 10 showed a few sweat pores but absent sweating, and 7 produced reduced sweat volumes (1e11 ml) as compared with controls (38e93 ml). Two of the low sweating XLHED subjects had normal sweat pore counts. In all 5 heterozygous females, some sweat was detected, but generally less than in female controls. Basal and stimulated skin conductance readings were reduced in 23 of 24 non-sweating, but only in 3 of 12 low-sweating XLHED subjects. There was no correlation between sweat production and number of missing teeth. Conclusions: In contrast to prior reports on nongenotyped hypohidrotic ectodermal dysplasia populations, this study confirmed a consistent, quantifiable defect of sweat gland function in male XLHED subjects as a disease biomarker. Among 26 different EDA genotypes, specific mutations were shown to be consistently associated with anhidrosis, implying that systematic mapping of EDA mutations together with the analysis of objective clinical data may help to distinguish functionally crucial mutations from those allowing residual activity of the gene product.
CRIS-Team Scopus Importer:2020-07-01

Sweating ability of patients with p63-associated syndromes - Ferstl, Paul; Wohlfart, Sigrun; Schneider, Holm (European Journal of Pediatrics, 2018)
Sweating deficiency has been reported to represent a cardinal symptom of ectrodactyly-ectodermal dysplasia-cleft lip/palate syndrome and ankyloblepharon-ectodermal dysplasia-cleft lip/palate syndrome, two rare p63-associated disorders. According to online resources, hypohidrosis may lead to most life-threatening complications in affected patients. Thus, counseling on the prevention of hyperthermia would be indispensable in case of such syndromes, although detailed information on this issue is missing in the literature. We investigated 14 individuals with ectrodactyly-ectodermal dysplasia-cleft lip/palate syndrome (age range 2-48 years) and 9 individuals with ankyloblepharon-ectodermal dysplasia-cleft lip/palate syndrome (0.5-60 years of age) by confocal laser scanning microscopy to determine their palmar sweat duct density and by quantification of pilocarpine-induced sweating. Genotype-phenotype correlations were assessed. In 12 of 23 patients (52%), a normal amount of sweat ducts was detected. These individuals (9 with ectrodactyly-ectodermal dysplasia-cleft lip/palate syndrome, 3 with ankyloblepharon-ectodermal dysplasia-cleft lip/palate syndrome) produced sufficient sweat volumes (≥ 20 μl) in response to pilocarpine. All other patients had clearly reduced sweating ability and fewer sweat glands, but no anhidrosis. Alteration of a specific proline residue (Pro590) of p63 was consistently linked to impaired perspiration.Conclusion: Hypohidrosis in p63-associated syndromes is less common and potentially less severe than previously thought and may be attributable to certain genotypes. What is Known: • Hypohidrosis which has been listed as a cardinal symptom of AEC and EEC syndromes may lead to life-threatening hyperthermia. What is New: • Patients with EEC and AEC syndromes often can sweat normally. • Hypohidrosis seems to be attributed to certain TP63 genotypes.
EVALuna2:35484

Systematic evaluation of exertional hyperthermia in children and adolescents with hypohidrotic ectodermal dysplasia: An observational study - Hammersen, Johanna E.; Neukam, Valentin; Nüsken, Kai-Dietrich; Schneider, Holm (Pediatric Research, 2011)
To evaluate exertional overheating and the impact of physical exercise on individuals with hypohidrotic ectodermal dysplasia (HED) and to assess protective effects of cooling devices, 13 boys and male adolescents with X-linked HED (XLHED) and age-matched healthy male controls were studied during standardized exercise on a bicycle ergometer at ambient temperatures of 25 and 30°C, without cooling and with evaporative skin cooling devices at 30°C. Body core temperature during and after exercise, heart rate, performance, endurance, and serum lactate were investigated. XLHED subjects experienced a significantly greater rise in body temperature after cycling than healthy controls, and their body temperature remained elevated longer. Maximum heart rates and lactate values did not differ significantly between XLHED and control groups. Application of skin cooling devices led to a clinically relevant attenuation of exertional hyperthermia in XLHED patients, and a previous tendency toward lower performance disappeared. This first systematic study of the effects of physical exercise on HED patients demonstrates a rapid and lasting body temperature increase in XLHED subjects after cycling, posing them at risk of exercise-induced hyperthermia. External evaporative skin cooling attenuates exertional overheating in HED patients and may facilitate their participation in athletic activities and professional life. Copyright © 2011 International Pediatric Research Foundation, Inc.
CRIS-Team Scopus Importer:2020-07-01

T Cell Impairment Is Predictive for a Severe Clinical Course in NEMO Deficiency - Heller, Stephanie; Kölsch, Uwe; Magg, Thomas; Krüger, Renate; Scheuern, Andrea; Schneider, Holm; Eichinger, Anna; Wahn, Volker; Unterwalder, Nadine; Lorenz, Myriam; Schwarz, Klaus; Meisel, Christian; et al. (Journal of Clinical Immunology, 2020)
Purpose: NEMO-deficient patients present with variable degrees of immunodeficiency. Accordingly, treatment ranges from antibiotic prophylaxis and/or IgG-substitution to allogenic hematopoietic stem cell transplantation (HSCT). The correct estimation of the immunodeficiency is essential to avoid over- as well as under-treatment. We compare the immunological phenotype of a NEMO-deficient patient with a newly-described splice site mutation that causes truncation of the NEMO zinc-finger (ZF) domain and a severe clinical course with the immunological phenotype of three NEMO-deficient patients with missense mutations and milder clinical courses and all previously published patients. Methods: Lymphocyte subsets, proliferation, and intracellular NEMO-expression were assessed by FACS. NF-κB signal transduction was determined by measuring IκBα-degradation and the production of cytokines upon stimulation with TNF-α, IL-1β, and TLR-agonists in immortalized fibroblasts and whole blood, respectively. Results: The patient with truncated ZF-domain of NEMO showed low levels of IgM and IgG, reduced class-switched memory B cells, almost complete skewing towards naïve CD45RA+ T cells, impaired T cell proliferation as well as cytokine production upon stimulation with TNF-α, IL-1β, and TLR-agonists. He suffered from severe infections (sepsis, pneumonia, osteomyelitis) during infancy. In contrast, three patients with missense mutations in IKBKG presented neither skewing of T cells towards naïvety nor impaired T cell proliferation. They are stable on prophylactic IgG-substitution or even off any prophylactic treatment. Conclusion: The loss of the ZF-domain and the impaired T cell proliferation accompanied by almost complete persistence of naïve T cells despite severe infections are suggestive for a profound immunodeficiency. Allogenic HSCT should be considered early for these patients before chronic sequelae occur.
CRIS-Team Scopus Importer:2020-02-04
Keywords: CD45RA; immunological phenotype; NEMO deficiency; Primary immunodeficiency; T cell deficiency

The EDELIFE clinical trial, the first investigation of a signalling molecule to treat in utero a human developmental genetic disorder - Schneider, Holm; Hadj-Rabia, Smail; Faschingbauer, Florian; Bodemer, Christine; Grange, Dorothy K.; Guillén-Navarro, Encarna; Tadini, Gianluca; Clarke, Angus (European Journal of Human Genetics, 2024)

The nuclear receptor constitutive androstane receptor/NR1I3 enhances the profibrotic effects of transforming growth factor β and contributes to the development of experimental dermal fibrosis - Avouac, Jerome; Palumbo-Zerr, Katrin; Ruzehaji, Nadira; Tomcik, Michal; Zerr, Pawel; Dees, Clara; Distler, Alfiya; Beyer, Christian; Schneider, Holm; Distler, Oliver; Schett, Georg; Allanore, Yannick; et al. (Arthritis and Rheumatology, 2014)
Objective Nuclear receptors regulate cell growth, differentiation, and homeostasis. Selective nuclear receptors promote fibroblast activation, which leads to tissue fibrosis, the hallmark of systemic sclerosis (SSc). This study was undertaken to investigate the effects of constitutive androstane receptor (CAR)/NR1I3, an orphan nuclear receptor, on fibroblast activation and experimental dermal fibrosis. Methods CAR expression was quantified by quantitative polymerase chain reaction, Western blotting, immunohistochemistry, and immunofluorescence. CAR expression was modulated by small molecules, small interfering RNA, forced overexpression, and site-directed mutagenesis. The effects of CAR activation were analyzed in cultured fibroblasts, in bleomycin-induced dermal fibrosis, and in mice overexpressing a constitutively active transforming growth factor β (TGFβ) receptor type I (TβRI-CA). Results Up-regulation of CAR was detected in the skin and in dermal fibroblasts in SSc patients. Stimulation of healthy fibroblasts with TGFβ induced the expression of CAR messenger RNA and protein in a Smad-dependent manner. Pharmacologic activation or overexpression of CAR in healthy fibroblasts significantly increased the stimulatory effects of TGFβ on collagen synthesis and myofibroblast differentiation, and amplified the stimulatory effects of TGFβ on COL1A2 transcription activity. Treatment with CAR agonist increased the activation of canonical TGFβ signaling in murine models of SSc and exacerbated bleomycin-induced and TβRI-CA-induced fibrosis with increased dermal thickening, myofibroblast counts, and collagen accumulation. Conclusion Our findings indicate that CAR is up-regulated in SSc and regulates TGFβ signaling. Activation of CAR increases the profibrotic effects of TGFβ in cultured fibroblasts and in different preclinical models of SSc. Thus, inactivation of CAR might be a novel approach to target aberrant TGFβ signaling in SSc and in other fibrotic diseases.
CRIS-Team Scopus Importer:2020-07-01

The ovine cerebral venous system: comparative anatomy, visualization, and implications for translational research - Hoffmann, Anke; Stoffel, Michael H.; Nitzsche, Bjoern; Lobsien, Donald; Seeger, Johannes; Schneider, Holm; Boltze, Johannes (PLoS ONE, 2014)
Cerebrovascular diseases are significant causes of death and disability in humans. Improvements in diagnostic and therapeutic approaches strongly rely on adequate gyrencephalic, large animal models being demanded for translational research. Ovine stroke models may represent a promising approach but are currently limited by insufficient knowledge regarding the venous system of the cerebral angioarchitecture. The present study was intended to provide a comprehensive anatomical analysis of the intracranial venous system in sheep as a reliable basis for the interpretation of experimental results in such ovine models. We used corrosion casts as well as contrast-enhanced magnetic resonance venography to scrutinize blood drainage from the brain. This combined approach yielded detailed and, to some extent, novel findings. In particular, we provide evidence for chordae Willisii and lateral venous lacunae, and report on connections between the dorsal and ventral sinuses in this species. For the first time, we also describe venous confluences in the deep cerebral venous system and an 'anterior condylar confluent' as seen in humans. This report provides a detailed reference for the interpretation of venous diagnostic imaging findings in sheep, including an assessment of structure detectability by in vivo (imaging) versus ex vivo (corrosion cast) visualization methods. Moreover, it features a comprehensive interspecies-comparison of the venous cerebral angioarchitecture in man, rodents, canines and sheep as a relevant large animal model species, and describes possible implications for translational cerebrovascular research.
EVALuna2:18907

Umbilical cord blood stem cells: Induction of differentiation into mesenchymal lineages by cell-cell contacts with various mesenchymal cells - Park, Jung; Setter, Viviane; Wixler, Viktor; Schneider, Holm (Tissue Engineering - Part A, 2009)
CD133(+) cells isolated from bone marrow, peripheral blood, or umbilical cord blood (UCB) represent an established source of transplantable hematopoietic progenitors. Further, there is increasing evidence that such CD133(+) cell isolates comprise subpopulations capable of differentiating into several mesenchymal lineages. In this study, we investigated conditions under which mesenchymal differentiation can be induced, particularly the role of cell-cell contacts with mesenchymal cells. A purified, nearly homogeneous CD133(+) population of human UCB cells was expanded by stimulation with platelet-derived growth factor and epidermal growth factor, labeled with the fluorescent marker DiI and cocultivated with rat osteoblasts, C2C12 myoblasts, or rat cardiomyocytes, respectively. In control experiments, the two cell types were separated by microporous membranes to avoid cell-cell contacts. Direct coculture of DiI-labeled UCB cells with the different mesenchymal cell populations resulted in both significant morphological changes and upregulation of lineage-specific markers. Expression of osteocalcin, myosin heavy chain, or α-actinin confirmed differentiation of the UCB cells into an osteoblastic, myoblastic, or cardiomyocytic phenotype, respectively. In contrast, coculture of UCB cells with the respective inducer cells under conditions preventing cell-cell contacts yielded minor, if any, evidence for such differentiation. Our data, thus, indicate that UCB cell expansion in vitro and subsequent direct cell-cell contacts with mesenchymal cells can induce their differentiation into mesenchymal lineages specific to the cell type they are in contact with. This finding has important implications for understanding the homing of adult stem cells and the promise of UCB as a cell source for tissue engineering and regenerative medicine. © 2009, Mary Ann Liebert, Inc.
CRIS-Team Scopus Importer:2020-07-01

Unbound corneocyte lipid envelopes in 12R-lipoxygenase deficiency support a direct role in lipid-protein crosslinking - Meyer, J. M.; Crumrine, D.; Schneider, Holm; Dick, Angela; Schmuth, M.; Gruber, R.; Radner, F.; Grond, S.; Wakefield, J.; Mauro, T.; Elias, P. (JOURNAL OF INVESTIGATIVE DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-28

Unbound Corneocyte Lipid Envelopes in 12R-Lipoxygenase Deficiency Support a Specific Role in Lipid-Protein Cross-Linking - Meyer, Jason M.; Crumrine, Debra; Schneider, Holm; Dick, Angela; Schmuth, Matthias; Gruber, Robert; Radner, Franz P.W.; Grond, Susanne; Wakefield, Joan S.; Mauro, Theodora M.; Elias, Peter M. (American Journal of Pathology, 2021)
Loss-of-function mutations in arachidonate lipoxygenase 12B (ALOX12B) are an important cause of autosomal recessive congenital ichthyosis (ARCI). 12R-lipoxygenase (12R-LOX), the protein product of ALOX12B, has been proposed to covalently bind the corneocyte lipid envelope (CLE) to the proteinaceous corneocyte envelope, thereby providing a scaffold for the assembly of barrier-providing, mature lipid lamellae. To test this hypothesis, an in-depth ultrastructural examination of CLEs was performed in ALOX12B−/− human and Alox12b−/− mouse epidermis, extracting samples with pyridine to distinguish covalently attached CLEs from unbound (ie, noncovalently bound) CLEs. ALOX12B−−/− stratum corneum contained abundant pyridine-extractable (ie, unbound) CLEs, compared with normal stratum corneum. These unbound CLEs were associated with defective post-secretory lipid processing, and were specific to 12R-LOX deficiency, because they were not observed with deficiency of the related ARCI-associated proteins, patatin-like phospholipase 1 (Pnpla1) or abhydrolase domain containing 5 (Abhd5). These results suggest that 12R-LOX contributes specifically to CLE–corneocyte envelope cross-linking, which appears to be a prerequisite for post-secretory lipid processing, and provide insights into the pathogenesis of 12R-LOX deficiency in this subtype of ARCI, as well as other conditions that display a defective CLE.
CRIS-Team Scopus Importer:2021-05-07

Variants of the ectodysplasin A1 receptor gene underlying homozygous cases of autosomal recessive hypohidrotic ectodermal dysplasia - Wohlfart, Sigrun; Schneider, Holm (Clinical Genetics, 2019)
Hypohidrotic ectodermal dysplasia (HED) is a rare genetic condition resulting from defective development of ectodermal derivatives, such as hair, teeth, and sweat glands. Autosomal recessive (AR) forms of HED may be caused by pathogenic variants of the ectodysplasin A1 receptor (EDAR) gene that encodes a receptor involved in the NF-kappa B signaling pathway. Here, we describe three cases of AR-HED in families of Turkish, Austrian, and German-American origin (with or without known consanguinity). In these cases, two out-of-frame deletions and a pathogenic missense variant of EDAR were found to be disease-causing due to reduced availability of the respective messenger RNA or impaired interaction of the encoded protein with its binding partner leading to diminished signal transduction. The same missense variant, c.1258C>T (p.Arg420Trp), has actually been reported to be restricted to the Icelandic population and to be associated with non-syndromic tooth agenesis but not HED. As our patient has no known relationship to Icelandic individuals and displays a rather severe HED phenotype, we suggest that EDAR-Arg420Trp is a more widespread variant, possibly with variable clinical expressivity.
CRIS-Team WoS Importer:2019-03-06

What Is and Isn’t an Ectodermal Dysplasia? - Peschel, Nicolai; Schneider, Holm (Springer Nature, 2025)
This chapter discusses the classification of ectodermal dysplasias, which has evolved over decades from one based purely on clinical symptoms to one based on molecular changes and signaling pathways. As there are many different disease entities and a broad spectrum of clinical manifestations, a distinctive classification according to the molecular pathways or the cell structures involved is not only useful but has become the gold standard for classifying any group of rare genetic diseases. The general transition from a descriptive clinical to a molecular approach occurred because user-friendly and accessible molecular diagnostic tests are now available in almost every diagnostic laboratory and because the identification of pathogenic gene variants can often quickly objectify a clinical suspicion, allowing better comparability of the different patients seen by healthcare professionals.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Classification; Criteria; Syndromes

X-chromosomal insertions at a recurrent site causing ectodermal dysplasia - Schneider, Holm; Mühle, Christiane (European Journal of Dermatology, 2009)
CRIS-Team Scopus Importer:2020-07-01